Self-healing concrete: investigating the synergistic effects of Bacillus subtilis and silica fume - Aayzaz Ahmed; Mirza Aamish Hassan Khan; Milica Vidak Vasić; Mehroz Imtiaz; Arslan Shabir; Tariq Ali; Muhammad Zeeshan Qureshi; Anwar Ahmed (European Journal of Environmental and Civil Engineering, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Slope gradients mediate the effects of newly returned crop residues on soil nutrient dynamics and microbial diversity in Mollisol maize monoculture systems in Northeast China - Anwar Zeb; Liang-Jun Hu; Xu Li; Gohar Ali; Atteqa Akbar; Sarfraz Ahmed; Muhammad Awais Haider; Amrozia Naz (Agriculture, Ecosystems & Environment, 2026)

Nano-formulated β-glucans from Saccharomyces cerevisiae enhance immunity and protection against coccidiosis in broiler chickens - Muhammad Noor; Muhammad Irfan Anwar; Mian Muhammad Awais; Masood Akhtar; Faqir Muhammad (Veterinary Parasitology, 2026)

Microplastics and co-occurred heavy metal contamination in rivers nearby industrial areas - Noverita Dian Takarina; Andrio Adiwibowo; Muhammad Zulfikar Anwar (Regional Studies in Marine Science, 2026)

Intelligent machine learning solutions with Bayesian regularization backpropagation adaptive networks for differential systems of Maize streak virus diseases - Nabeela Anwar; Aqsa Ghaffar; Muhammad Asif Zahoor Raja; Iftikhar Ahmad; Muhammad Shoaib; Adiqa Kausar Kiani (Mathematical Biosciences, 2026)

Engineering MXene-based platforms for electrocatalytic CO2 and N2 reduction reactions; synthesis, modification strategies, and mechanistic insights - Sami Ur Rahman; Saeed Anwar; Awal Noor; Sadaf Qayyum; Yelubay Madeniyet; Niaz Muhammad (Journal of Environmental Chemical Engineering, 2026)

Mechanistic evaluation of electrocoagulation pre-treatment for reducing calcium–magnesium scaling during non-oily refinery wastewater treatment - Kanwal Anwar; Muhammad Saqib Nawaz; Sher Jamal Khan; Noreddine Ghaffour; Momina Maheen (Journal of Environmental Chemical Engineering, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Adaptive strategies of Tamarix aphylla in hyper-saline conditions of Cholistan Desert - Muhammad Akram; Nargis Naz; Hafiz Muhammad Mohsin Hassan; Maqbool Ahmed; Leman Aliyeva; Muhammad Yousaf Nadeem; Hind Saad Alsubaie; Sahar Anwar Almalki; Abdelrahman R. Ahmed; Abdullah R. Alanzi (The Science of Nature, 2026)

Kollidon® SR–Stearic Acid Based Thermoresponsive Solid Lipid Nanoparticles for Dual Cisplatin–Epirubicin Delivery: Formulation Development and In-Vitro Evaluation - Farrukh Mehmood; Muhammad Imran Khan; Zulcaif Ahmad; Muhammad Furqan Akhtar; Fareeha Anwar; Tassawer-e-Meran (Journal of Pharmaceutical Innovation, 2026)

Rationalizing bud load for grapevine cv sugraone for balanced yield and superior fruit quality in a warm semi-arid region - Muhammad Hashir Khan; Irfan Ali; Muhammad Tahir Akram; Mahmood-ul-Hassan; Adeel Anwar; Rizwan Rafique (Acta Physiologiae Plantarum, 2026)

Microbe-mediated drought stress alleviation: Fusarium verticillioides enhances maize growth by upregulation of physiological, biochemical, and molecular responses - Raid Ali; Humaira Gul; Mamoona Rauf; Sajid Ali; Muhammad Arif; Sumera Afzal Khan; Anwar Hussain; Bokyung Lee; Muhammad Hamayun (South African Journal of Botany, 2026)

Bimetallic ferro and lanthanum impregnated on nano HZSM-5 catalysts for the Reutealis trisperma oil hydroprocessing to rich aromatic jet fuel range - Muhammad Al Muttaqii; Abdul Aziz; Sugeng Priyanto; Indri Yati; Muh. Nur Khoiru Wihadi; Amalia Kurnia Amin; Kiky Corneliasari Sembiring; Hendris Hendarsyah Kurniawan; Sudibyo; Didik Prasetyoko; Reva Edra Nugraha; Lenny Marlinda; et al. (Bioresource Technology Reports, 2026)

Transient fractional Brinkman–Forchheimer flow in fractures with porous infill and prescribed shear-induced aperture changes: A robust numerical framework and transmissivity implications - Mumtaz Khan; M.S. Anwar; Sharifah E. Alhazmi; Taseer Muhammad (Advances in Water Resources, 2026)

Plio-Pleistocene environmental shifts in the Bumiayu sub-basin revealed by mollusca and facies records: The environmental setting of a potential coastal dispersal route for large mammals into Sundaland - Harman Dwi Rachmadhan; Aswan; Khoiril Anwar Maryunani; Alfend Rudyawan; Muhammad Wildan Fadhillah; Eugenius Olafianto Drespriputra Wisnuwardhana; Taufiqurrahman Setiawan; Yves Belgiaswara Susilo; Eduard Pop; H.J.L. van der Lubbe; Thomas Ingicco; Thomas Sutikna; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Harnessing biostimulants to alleviate potentially toxic element stress in vegetable crops - Amna Jamil; Waqas Liaqat; Asia Maqbool; Pramod Sargar; Muhammad Anwar-Ul-Haq; Shraddha Samindre; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed; Muhammad Tanveer Altaf (Planta, 2026)

Mineralogical and microstructural characterization of lithium-bearing ore from Gilgit-Baltistan, Pakistan - Muhammad Yousif; Jehanzaib Anwar; Razia Kalsoom; Ammarah Kanwal; Muhammad Azam; Muhammad Afzal; Farooq Ahmed; Syed Hussain Imam Abidi (Arabian Journal of Geosciences, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Nickel and Cobalt Accumulation and Human Health Risk in Guava (Psidium guajava L.) Under Wastewater Irrigation: A Soil–Plant Transfer Assessment - Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Sana Anwar; Shahzad Akhtar; Ijaz Rasool Noorka; Muhammad Irfan Ashraf; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Deciphering the structural–functional dynamics of glucosyltransferases from novel Apilactobacillus isolates through in silico analysis - Hira Kiran; Munir A. Anwar; Waqar Ahmad; Iqra Jawad; Ayesha Siddiqa; Muhammad Imran; Moazur Rahman; Muhammad Saleem (Biologia, 2026)

Plant growth-promoting rhizobacteria (PGPR) producing ACC deaminase and exopolysaccharides enhance salt tolerance in wheat - Mahnoor Hayat; Rashida Parveen; Muhammad Shoib Nawaz; Muhammad Ahmad Rao; Ahmed Waqar; Rubab Zahra. Naqvi; Munir Ahmad Anwar; Zahir Ahmad Zahir; Muhammad Qasim; M Ahmad Dogar; Tadeo Sáez Sandino; Brajesh K. Singh; et al. (World Journal of Microbiology and Biotechnology, 2026)

Factors influencing circular economy adoption in Pakistan’s construction industry - Rai Waqas Azfar; Mohsin Shah; Mughees Aslam; Muhammad Sohail Anwar Malik; Hamza Alam (Environment, Development and Sustainability, 2026)

Evaluation of host suitability and larval instar effects on the reproductive potential of entomopathogenic nematodes against lepidopteran pests - Hina Safdar; Sumaira Maqsood; Salman Ghuffar; Aftab Ahmad; Muhammad Hafeez; Hifza Safdar; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Ibrokhim Ismoilov; Feruza Tukhtaboeva; Nazih Y. Rebouh; et al. (Crop Protection, 2026)

Deciphering the synergy of eudragit and polyethylene glycol supported cobalt oxide for catalytic, electrocatalytic and antibacterial activity: Computational insights - Atika; Muhammad Imran; Iram Shahzadi; Ali Haider; Sumaira Rasool; Anwar Ul-Hamid; Norah A. Albassami; Muhammad Ikram (Journal of Water Process Engineering, 2026)

Enhancing proton conduction through SLZO-LCO pn-Junction heterostructures in semiconductor ionic membrane fuel cells - Yuqi Zhou; Touseef Ahmad; Kashf Zman; Hafsa Mansha; Muhammad Faisal Anwar; Peng Zhou; Lian Chen; Haijun Wang; Yuran Qi; Yuzheng Lu (Fuel, 2026)

Biomass-derived porous carbon supported CuCo alloy for efficient electrocatalytic nitrate reduction to ammonia - Abdulla Eziz; Yusan Turap; Abulikemu Abulizi; Changhai Liang; Wenli Zhu; Kenji Okitsu; Anwar Mamat; Aisha Nulahong; Imran Muhammad; Tiezhen Ren (Chemical Engineering Journal, 2026)

Integrative screening of cotton genotypes against salt stress using pre-breeding and machine learning methods - Zunaira Anwar; Sajid Shokat; Allah Ditta; Muhammad Kashif Riaz Khan (Biocatalysis and Agricultural Biotechnology, 2026)

Chinese milk vetch as green manure enables simultaneous NPK fertilizer reduction while enhancing rice yield and soil fertility in subtropical systems - Tahir Shah; Muhammad Sufhan Tahir; Adnan Anwar Khan; Muhammad Fraz Ali; Sadam Khan; Muhammad Riaz; Yajun Gao; Qiang Zhu (Applied Soil Ecology, 2026)

Correction to: Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Rational Design of SFT-Based Hole Transport Materials with Diversified Terminal Acceptors for Efficient Perovskite Solar Cells: A DFT Study - Aqsa Laraib; Tazeem Fatima; Shumaila Shaheen; Natasha Anwar; Muhammad Imran; M. Fakhar-e-Alam; Nabeel Shahzad (Journal of Fluorescence, 2026)

Biomass-derived biochar as a precursor for graphene-like carbon materials via slow pyrolysis: A review - Illa Rizianiza; Eny Kusrini; Ahmad Indra Siswantara; Muhammad Aziz; Ponky Ivo; Imam Jauhari Maknun; Rendika Rumaldin Ichsan; Kuntum Khoiro Ummatin; Anwar Usman (Journal of Environmental Chemical Engineering, 2026)

High-sensitive electrochemical assay for endocrine disruptor bisphenol A detection based on graphene/TiO2-S nanohybrid modified sensor - Irwan Irwan; Anwar Anwar; Wenkey Mangera P; Muhammad Nurdin; Maulidiyah Maulidiyah; Muhammad Zakir Muzakkar (Environmental Nanotechnology, Monitoring & Management, 2026)

Coral disease diversity and observed prevalence in the Seram Laut Islands, Indonesia - Mujiyanto Mujiyanto; Andrias S. Samusamu; Ofri Johan; Reny Puspasari; Masayu Rahmia Anwar Putri; Tirtadanu Tirtadanu; Yayuk Sugianti; Karsono Wagiyo; Muhammad Taufik; Puput Fitri Rachmawati; Prihatiningsih Prihatiningsih; Rita Rachmawati; et al. (Continental Shelf Research, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Nanoparticles in Vegetable Production: From Soil to Human Health - Amna Jamil; Muhammad Tanveer Altaf; Ishtiaq Ahmad; Waqas Liaqat; Asia Maqbool; Muhammad Anwar-Ul-Haq; Pramod Sargar; Heba I. Mohamed; Faheem Shehzad Baloch (Water, Air, & Soil Pollution, 2026)

Integrated hydrochemical and health-risk assessment of fluoride and major ions in groundwater from hattar and gadoon industrial estates, pakistan - Tofeeq Ahmad; Anwar Qadir; Muhammad Azam Khan; Nabeel Akhtar; Alaa Ahmed (Environmental Geochemistry and Health, 2026)

Synergistic biocontrol of Parthenium hysterophorus: the role of Curvularia specifera and Zygogramma bicolorata - Syed Muhammad Ziaullah; Muhammad Hamayun; Amjad Iqbal; Syed Asim; Sajid Ali; Anwar Hussain (Archives of Microbiology, 2026)

Enhanced Antimicrobial Photodynamic Effect Against Escherichia coli Using MXene-Based Silver–Curcumin 2D Nanocomposite Photosensitizers - Saliha Noor; Shahzad Anwar; Rafaqat Ali Khan; Sawera Malik; Hina Ali; Farwa Nurjis; Shaista Taimur; Muhammad Iftikhar; Muhammad Saleem; Babar Manzoor Atta (Journal of Fluorescence, 2026)

The role of jasmonic acid in enhancing drought resilience in mangroves: from signaling to restoration - Yi Han; Muqadas Noor; Meng Ying Huang; Wenna Wang; Muhammad Anwar; Yanjun Du (South African Journal of Botany, 2026)

Biogenic silver-selenium nanocomposites as an effective and sustainable alternative for controlling citrus canker - Iqra Ilyas; Hammad Ul Hassan; Naveed Iqbal Raja; Zia-Ur-Rehman Mashwani; Hossam S. El-Beltagi; Muhammad Sheeraz Ahmad; Huma Qureshi; Tauseef Anwar; Muhammad Iqbal; Khalid H. Alamer; Nazih Y. Rebouh; Bakhrom Jobborov; et al. (Physiological and Molecular Plant Pathology, 2026)

Optimization and multivariate analysis of Schiff Base functionalized gold nanoparticle sensor for efficient bifenthrin detection in food samples - Syeda Bushra Anwar; Sana Yaqoob; Sufian Rasheed; Shujaat Ali; Abdul Rehman Umar; Kashif Hussain; Nazish Kousar; Kousar Yasmeen; Haji Muhammad; Abdul Hameed (Food Chemistry, 2026)

Balancing Nutrient Enrichment and Heavy Metal Stress: Impacts of Wastewater Irrigation on Aromatic Crops - Rabia Bibi; Mehmooda Munazir; Amina Kanwal; Muhammad Farhan; Rahmatullah Qureshi; Tauseef Anwar; Huma Qureshi; Shujat Ali; Hossam S. El-Beltagi; Dilbar Bazarbayeva; Ibtisam M. Alsudays; Khalid H. Alamer; et al. (Environmental Monitoring and Assessment, 2026)

Effect of surface modification of stainless steel mesh anode with α-MoO3 on the performance of membrane less single chamber microbial fuel cell - Omamah Tayyabah; Mustafa Anwar; Muhammad Hassan; S.A Muhammed Ali; Ali Bahadar (Sustainable Chemistry and Pharmacy, 2026)

Coupled seepage stress analysis and design optimization of deep buried subsea tunnels - Mumtaz Khan; Muhammad Shoaib Anwar; Taseer Muhammad; Taoufik Saidani (Ocean Engineering, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Integrative Molecular and Structural Profiling of Escherichia coli Virulence Genes in Diabetes-Associated Infections - Noor Jahan Begum; Muhammad Qasim; Ihtisham Ul Haq; Hassan Naveed; Farhan Anwar Khan; Zahid Ullah Khan; Farman Ullah Dawar (Current Microbiology, 2026)

Modulation of arsenic uptake and detoxification in maize (Zea mays L.) by plant-based iron oxide nanoparticles - Tauseef Anwar; Huma Qureshi; Muhammad Imran; Hossam S. El-Beltagi; Salohiddinjon Yunusov; Shuqurillo Ziyadov; Muydinjon M. Muminov; Gamal Awad El-Shaboury; Dilbar Bazarbayeva; Ibtisam M. Alsudays; Khalid H. Alamer; Munisa Bekmukhamedova; et al. (Biodegradation, 2026)

mcr gene family evolution and structural mechanisms of colistin resistance: from mcr-1 to emerging variants - Muhammad Shahid Mehmood; Uthpala Kavindi Rupasinghe Koggala Marakkalage; Tabish Arif; Fariha Javaid; Muhammad Ali Abid; Muntha Shahid; Anwar Parvez; Muhammad Nabeel Saddique; Sultan Ali (Archives of Microbiology, 2026)

Advances in Understanding Cold Tolerance Mechanisms in Potato (Solanum Tuberosum L.): Physiological, Biochemical, Molecular, and Breeding Perspectives - Barkat Ali; Wajid Anwar; Muhammad Nauman Khan (American Journal of Potato Research, 2026)

Optimization of Tissue Culture Media for Microtuber Development Incorporating Sugars and Zinc Nanoparticles - Muzammil Anwar Khan; Naima Huma Naveed; Aamir Ali; Muhammad Adeel; Aima Iram Batool; Tahir Shahzad; Muhammad Rizwan Khan; Salman Majeed (American Journal of Potato Research, 2026)

Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Deciphering water scarcity footprint of auxiliary paddy irrigation via Available Water Remaining (AWARE)-LCA model for sustainable groundwater infrastructure - Naseem Akhtar; Abdulghani Essyah Musbah Swesi; Syahidah Akmal Muhammad; Muhammad Izzuddin Syakir; Raed Sameeh Raja Hussain; Pahmi Husain; Ateyah Alzahrani; Anwar Ulla Khan; Ahmad Alghamdi (Environmental Monitoring and Assessment, 2026)

Evaluation of Heavy Metal Contamination in Indus Deltaic Creeks Sediments, Sindh, Pakistan: Ecological Risk Assessment and Environmental Implications - Syed Muhammad Rehan Ullah; Syed Muhammad Saqib Nadeem; Sanober Kahkashan; Abdullah; Anwar Zeb (Marine Pollution Bulletin, 2026)

Enhance soil phosphorus availability via the growth and decomposition of green manure crops in drylands - Gaohai Han; Rana Muhammad Ammar Asghar; Adnan Anwar Khan; Yupei Chen; Jiarong Wang; Shijie Wei; Chenxi Liu; Zhiqi Li; Zhaohui Wang; Donglin Huang; Xiaomin Wei; Weidong Cao; et al. (Soil and Tillage Research, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic Effect of Biochar and Bacillus Subtilis on the Development of Colletotrichum Graminicola in Maize - Nimra Nadeem; Adnan Akhter; Waheed Anwar; Tehmina Anjum; Muhammad Khurshid; Nasir Ali; Sana Javed; Hibba Arshad (Journal of Soil Science and Plant Nutrition, 2026)

Enhancing village-level spatial planning with unmanned aerial vehicles: A comparative study of direct georeferencing and ground control points - Gunawan Setyo Prabowo; Suprapedi Suprapedi; Muhammad Bisri; Wayan Firdaus Mahmudy; Ari Sugeng Budiyanta; Nur Sugi; Try Kusuma Wardana; Aries Asrianto Ramadian; Hartono Hartono; Rudi Choirul Anwar; Unggul Satrio Yudhotomo (Applied Geomatics, 2026)

Greener hydrogen production and storage revolution towards a low-carbon future: an overview of current scenarios and future prospects - Tahir Rasheed; Sameera Shafi; Muhammad Tuoqeer Anwar; Hifsa Khurshid; Ahmad Naveed; Adil Alshoaibi; Nisrin Alnaim; Yunjian Liu; Tauqir A. Sherazi (Fuel, 2026)

Machine learning-based dual-parameter inversion for estimating snowpack liquid water content and density using common offset GPR data - Zohaib Akbar; Yuanjun Jiang; Ryan Webb; Anja Klotzsche; Yuanjia Zhu; Aftab Anwar; Muhammad Mudassar Rehman (Science China Earth Sciences, 2026)

A Snapshot of Brucellosis as an Occupational Health Hazard in Animal Handlers of an Agroecological Zone of Southern Punjab, Pakistan - Abdul Sammad Ali Khan Shirwany; Mian Muhammad Awais; Saad Masood; Aayesha Riaz; Masood Akhtar; Hosny El-Adawy; Faqir Muhammad; Muhammad Irfan Anwar; Mamoona Chaudhry (Journal of Agromedicine, 2026)

Neuroprotective Effects of Ficus deltoidea in Alzheimer’s Disease-Like Rat Model: Insights from Behavior, Histology, and Amyloid Pathology - Abdulhamid Sani Usman; Sushmitaa Dhevii Manoharan; Che Mohd Nasril Che Mohd Nassir; Hafizah Abdul Hamid; Zaw Myo Hein; Anwar Norazit; Jayakumar Murthy; Murizal Zainol; Mohd Amir Kamaruzzaman; Samaila Musa Chiroma; Muzaimi Mustapha; Mohamad Aris Mohd Moklas; et al. (Molecular Neurobiology, 2026)

Aspergillus Welwitschiae Regulates Response of Wheat at Multiple Levels To Alleviate Induced Chromate Stress - Urooj Jamal; Zia Ur Rahman; Muhammad Qadir; Muhammad Hamayun; Sajid Ali; Anwar Hussain (Current Microbiology, 2026)

Evaluation of the preventive effects of turmeric–ginger–oregano supplementation on DMBA-induced breast cancer in Sprague-Dawley rats - Nadeem Anwar; Salma Sultana; Muhammad Ashir Zia (Advances in Traditional Medicine, 2025)

Biocontrol potential of Bacillus subtilis Sjb3 against Rosa chinensis and apple diseases - Xiyan Lou; ManYu Chen; Ping Li; Yixue Cui; Chunhua Zhu; Dongdong Yu; Muhammad Anwar; Dongli Pei (Fungal Biology, 2025)

Pathogenic and clinical significance of inflammation-associated MicroRNAs in cardiovascular diseases - Arouj Anwar; Muhammad Jawad Khan (Molecular Biology Reports, 2025)

Organic Amendments Enhance Growth and Antioxidative Responses of Wheat (Triticum aestivum L.) Under Water Stress Conditions - Muhammad Tayyab Mehmood; Muhammad Anwar-ul-Haq; Muhammad Zia-ur-Rehman; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

P-solubilising bacteria and P-cycling genes drive soil P transformation during green manure decomposition - Adnan Anwar Khan; Yupei Chen; Rana Muhammad Ammar Asghar; Imran Azeem; Tahir Shah; Weidong Cao; Dabin Zhang; Yajun Gao (Agriculture, Ecosystems & Environment, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Phytoremediation potential of native tree species for lead removal under domestic wastewater irrigation: a nature-based solution for urban water pollution - Amina Kanwal; Muhammad Farhan; Mehmooda Munazir; Hossam S. El-Beltagi; Qaiser Farid Khan; Qamar uz Zaman; Huma Qureshi; Tauseef Anwar; Wajid Zaman; Dilbar Bazarbayeva; Khairiah Mubarak Alwutayd; Muneera A. Saleh; et al. (Environmental Monitoring and Assessment, 2025)

A rapid screening method for detection of ampicillin residues in dairy milk - Nida Noreen; Bushra Akhtar; Chi-Chung Chou; Muhammad Irfan Anwar; Mian Muhammad Awais; Faqir Muhammad (Research in Veterinary Science, 2025)

Integrating flue gas into membrane-based oxygen-enriched gasification of municipal solid wastes for enhancing waste-to-energy conversion - Chong Yang Chuah; Siti Nurhawa Binte Muhammad Anwar; Piyarat Weerachanchai; Tae-Hyun Bae; Kunli Goh; Rong Wang (Fuel, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Distinct impact of oxidation reactions on the evolution of pore structures during H3PO4 activation of aliphatic-rich poplar and aromatic-rich lignin - Qurshia Choudhry; Mengjiao Fan; Zahra Essa Khan; Baihong Li; Shu Zhang; Zanib Anwar; Muhammad Rashid; Xun Hu (Biomass and Bioenergy, 2025)

Retraction Note: The nexus between urbanization, renewable energy consumption, financial development, and CO2 emissions: evidence from selected Asian countries - Ahsan Anwar; Avik Sinha; Arshian Sharif; Muhammad Siddique; Shoaib Irshad; Waseem Anwar; Summaira Malik (Environment, Development and Sustainability, 2025)

Diversity of arthropods fauna in correlation to abiotic factors in wheat crop - Dilbar Hussain; Bushra Khalid; Muhammad Asrar; Usama Saleem; Wafa Abdullah Hamad Alkherb; Muhammad Saleem; Hina Anwar; Saddam Hussain; Muhammad Sohail Qadir; Mubshar Saleem; Khalid Ali Khan; Hamed A. Ghramh; et al. (International Journal of Tropical Insect Science, 2025)

Retraction notice to “Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles” [Environ. Res. 233 (2023) 116477] - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2025)

Mechanistic insights of facile synthesized-solar driven TiO2 intercalated 2D molybdenum disulfide evaporator for one-pot clean water production - Nurul Syazana Fuzil; Nur Hashimah Alias; Nur Hidayati Othman; Muhammad Shafiq Mat Shayuti; Norazah Abd Rahman; Zulkifli Abdul Rashid; Ahmad Fauzi Ismail; Anwar Ul-Hamid; Izumi Ichinose (Desalination, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Circular RNAs: Diversity, formation, functions, and identification mechanism with a focus on endogenous circular RNAs - Muhammad Umer; Naureen Anwar; Mustansar Mubeen; Yasir Iftikhar; Manoj Kumar Solanki; Muhammad Ahmad Zeshan; Khalid M. Alsyaad; Yun Li; Pingwu Liu (Physiological and Molecular Plant Pathology, 2025)

Effects of replacement of soybean meal with fermented soybean meal on growth performance, nutrient digestibility and carcass characteristics in broiler - Ali Husnain; Urooj Anwar; Asfa Fatima; Riaz Mustafa; Umar Farooq; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Aziz ur Rahman (Livestock Science, 2025)

Transcriptional variation of meat quality marker genes in different age and sex groups of Balkhi breed sheep - Muhammad Farooq Akhtar; Rajwali Khan; Syed Muhammad Suhail; Abdur Rehman; Ijaz Ahmad; Iftikhar Ahmad; Farhan Anwar Khan; Faraz Ahmad; Athar Rehman; Muhammad Ayaz; Khalid Khan; Amel Ayari-Akkari (Tropical Animal Health and Production, 2025)

Biochemical validation for the therapeutic use of Plumeria rubra in coagulation disorders: a study combining in silico, in vitro, and in vivo approaches - Imran Ahmad Khan; Muhammad Anwar; Sarmad Frogh Arshad; Athar Hussain; Muhammad Usman; Mohammed Nadeem Ansari; Hasan Junaid Arshad; Asma Shah Rukh; Qurat Ul Ain; Maliha Khalid Khan (Protoplasma, 2025)

Predicting Wheat Grain Yield Through Morphometric Analysis of Seed Dimensions Using Computational Imaging Techniques - Mahnoor; Muhammad Jamil; Aamir Ali; Tauseef Anwar; Huma Qureshi; Muhammad Tahir Naseem; Gadah Albasher; Mohammad Javed Ansari (Plant Molecular Biology Reporter, 2025)

Correction to: Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Exogenous Zinc Alleviates Post-Anthesis Heat Stress by Improving the Defense Mechanism and Leaf Physiology of Bread Wheat - Muhammad Sarwar; Muhammad Farrukh Saleem; Aleena Anwar; Hassaan Ahmad; Basharat Ali; Muhammad Shahid; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd-Allah (Journal of Soil Science and Plant Nutrition, 2025)

Genetic Variability Among Isolates of Curvularia lunata and Exserohilum rostratum Causing Brown Leaf Spot of Rice from Pakistan - Muhammad Faizan Anwar Khan; Abid Riaz; Rafia Ahsan; Ishaq Ahmad; Saif Ullah; Ahmed Raza; Muhammad Zakria (Current Microbiology, 2025)

Putrescine Detection Via PMMA-Zinc(II) Complex Optical Chemosensor: Meat Spoilage Screening Tool - Muhammad Ameerullah Sahudin; Jian Xiong Tan; Khairun Nasriah Azmi; Nur Afny Suhaimi; Shameer Hisham; Nor Kartini Abu Bakar; Muhammad Nidzhom Zainol Abidin; Khairul Anwar Ishak; Nurul Huda Abd Karim (Journal of Fluorescence, 2025)

Isolation, biochemical characterization, and antimicrobial activities of EPS-producing bacterial endophytes from Moringa oleifera - Karim Gul; Raham Sher Khan; Aneela Iqbal; Atta Ullah; Syed Muhammad Shafi Shah; Anwar Hussain; Douglas Law; Ayaz Ahmad; Salimullah Khan (Folia Microbiologica, 2025)

Endophytic Meyerozyma guilliermondii augmented growth attributes and metabolite production in Triticum aestivum under salinity stress - Zeeshan Khan; Muhammad Irshad; Anwar Hussain; Arshad Iqbal; Zamarud Shah; Waheed Murad; Eman R. Elsharkawy; Muhammad Nafees (Folia Microbiologica, 2025)

Enhanced electrocatalytic OER performance of Ba/CS-CoFe2O4 ternary heterostructure catalyst: Experimental and theoretical insights - Qirat Yameen; Muhammad Ikram; Sawaira Moeen; Muhammad Imran; Anwar Ul-Hamid; Ghafar Ali; Souraya Goumri-Said; Mohammed Benali Kanoun (Chemosphere, 2025)

Kojic acid suppresses browning incidence, maintains quality and sensory attributes of harvested loquat fruit by upregulating enzymatic and non-enzymatic antioxidants - Saqib Ayyub; Ahmad Sattar Khan; Raheel Anwar; Abdul Rehman; Hafiz Muhammad Shoaib Shah; Sajid Ali (Postharvest Biology and Technology, 2025)

An integrated evaluation framework for evaluating renewable-based building sector implementation in remote/off-grid areas with varying climatic zones - Rida Maryam; Syed Ali Abbas Kazmi; Muhammad Hassan; Mustafa Anwar (Energy and Buildings, 2025)

Molecular identification, risk factors’ assessment and phylogenetic analysis of Toxoplasma gondii in goats from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Ahmad Irshad; Shumaila Noreen; Uswa Sajid; Muhsin Jamal; Muhammad Anwar Iqbal; Ubaid Ullah; Talat Sabtain; Shakir Ullah; Eliana Ibañez-Arancibia; Patricio R. De Los Ríos-Escalante; Hanène Belkahia; Mourad Ben Said; et al. (Veterinary Research Communications, 2025)

Gum Arabic Organic Coating Maintains Freshness and Modulates Oxidative Stress by Augmenting the Antioxidant Activities of Harvested Ber Fruit - Alisha Noor; Ahmad Sattar Khan; Raheel Anwar; Sajid Ali; Rana Naveed Ur Rehman; Saqib Ayyub; Muhammad Haider Ali (Applied Fruit Science, 2025)

Synergistic performance of silver/polyacrylic acid doped ZrO2 nanostructures for dye degradation and bactericidal behavior with molecular docking analysis - Muhammad Ikram; Alvina Rafiq Butt; Sidra Bano; Sadia Naz; Sawaira Moeen; Anwar Ul-Hamid; Ali Haider; Amel Ayari-Akkari (Environment, Development and Sustainability, 2025)

Assessment of tomato germplasms for Mi-1.2-mediated resistance to Meloidogyne incognita: Integrating in-silico dynamics and bioinformatic approaches - Adil Zahoor; Zeenat Niaz; Muhammad Jabran; Hira Anwar; Amjad Abbas; Abdul Haseeb; Ghulam Mustafa; Sungmi Sun; Seung Hwan Yang; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Protease activated receptor inhibitors in rheumatoid arthritis: a new frontier in treatment - Tayyaba Rana; Huma Hameed; Ana Cláudia Paiva-Santos; Muhammad Jamshaid; Muneeba Anwar (Inflammopharmacology, 2025)

Differential effects of tomato root exudates on the development of endophytic and pathogenic fungi depend on the foliar application of fungi - Rainaz Parvez; Muhammad Hamayun; Asif Mehmood; Amjad Iqbal; Bokyung Lee; Anwar Hussain (Symbiosis, 2025)

Rosmarinic acid attenuates photophobia, hyperalgesia and neuroinflammation during nitroglycerine induced migraine like headache in mice - Maira Anwar; Ismail Badshah; Babar Murtaza; Syed Muzzammil Masaud; Umair Ilyas; Amber Kiyani; Danish Patoli; Muhammad Tariq Khan (Natural Product Research, 2025)

MXenes: From functional innovations to solving global environmental and energy crises – A comprehensive overview and perspective - Abdul Basit; Tahir Rasheed; Haiqa Maqsood; Sana Qureshi; Shaista Zubaid; Muhammad Tuoqeer Anwar; Ali Arishi; Tauqir A. Sherazi (Journal of Environmental Chemical Engineering, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Retraction notice to “Effects of vermicompost on soil microbiological properties in lettuce rhizosphere: An environmentally friendly approach for sustainable green future” [Environ. Res. 243 (2024) 117737] - Muhammad Danish Toor; Ridvan kizilkaya; Aneela Anwar; Lyubka Koleva; Gaber E. Eldesoky (Environmental Research, 2025)

Exploring the Role of Plant Growth-Promoting Bacteria in Biodegradation of Plastic: A Review - Haris Maqbool; Fazal Ur Rehman; Izhar Khan; Nadeem Ullah; Muhammad Anwar Sajad; Nazir Mohammad; Maria Kalsoom; Shafiq Ur Rehman; Muhammad Farooq Hussain Munis; Malka Saba; Hassan Javed Chaudhary (Water, Air, & Soil Pollution, 2025)

Exogenous Application of Nitrogen (N) and Potassium (K) Improves Drought Tolerance in Plants: A Review - Saira Sulaman; Muhammad Nadeem; Muhammad Shabaan; Sule Orman; Muhammad Anwar-ul-Haq; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)
With rising climate anomalies and deterioration of ecological balance, water shortage has emerged as a major environmental problem faced by mankind, which has considerably limited agricultural productivity worldwide. Drought stress generates an insidious hazard by destabilizing global hydrological cycle and due to its increased frequency, severity and associated adverse impacts on climate conditions, drought has obtained attention world over. Exposure to severe and acute drought stress disturbs physiological functioning of plants and inhibits the efficiency of photosynthetic system. As a result, lesser photosynthate production causes lower plant biomass and yield. Hence, it is imperative to sustain and improve plant growth and productivity under water shortage conditions to minimize its dreadful impacts. Current review summarizes the adverse impacts of drought stress on various agricultural crops, its alleviation strategies and various adaptations encountered by plants under drought stress. More importantly, current review emphasizes the beneficial roles played by macronutrients such as nitrogen (N) and potassium (K) in alleviating the adverse impacts of drought stress. As these essential nutrients have reportedly been involved in alleviating the negative impacts of drought stress on plant growth and therefore, major information in the current review article revolves around the N and K supply to the plant under drought stress. In addition, current review necessitates the use of optimum doses of N and K fertilizers to ensure maximum resource utilization efficiency and increased drought resilience.

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Engineering a complete mevalonate pathway in Chlamydomonas reinhardtii for enhanced isoprenoid production - Jingkai Wang; Muhammad Anwar; Jiancheng Li; Lin Dan; Bin Jia; Zhangli Hu (Algal Research, 2025)

Harvest Time Influences Quality and Storability of ‘Chandler’ Strawberries Grown Under Subtropical Conditions of Pakistan - Ayesha Maryam; Raheel Anwar; Mahmood Ul Hasan; Sajid Ali; Ahmad Sattar Khan; Muhammad Moaaz Ali; Khurram Ziaf (Applied Fruit Science, 2025)

Synthesis and Antibacterial Studies of Silver Loaded TiO2 Electrospun Nanofibers Against E. coli by Fluorescence Spectroscopy and Microscopy - Bisma Khanam; Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Muhammad Zakria; Taj Muhammad Khan; A. Rahman; Ahmad Adnan; Nida Ali Shan; Muhammad Raffi (Journal of Fluorescence, 2025)

Digital twins: cornerstone to circular economy and sustainability goals - Zain Anwar Ali; Mahreen Zain; Raza Hasan; Muhammad Salman Pathan; Hussain AlSalman; Faisal Abdulaziz Almisned (Environment, Development and Sustainability, 2025)
Accurate information is a prerequisite for circulation and greater longevity of materials and products, enabling the economically and environmentally successful transition of circular economy (CE) in the aspiration towards sustainable development. However, a lack of appropriate digital tools is noticed in supplying relevant information and supporting recyclability, reusability, and reducibility processes. This study focuses on a building block of evolving technologies anointed the digital twin (DT). It aims to conceptualize DT as a cornerstone for the CE paradigm, positively influencing sustainability. It also endeavors to scrutinize remarkable implementations of DT-driven CE, accomplishing sustainable development goals (SDGs) in Ireland. An iterative methodology based on four steps is adopted to review an explosion of relevant, recent literature published in 2019–2024 and multiple case studies of Irish construction and manufacturing sectors. By analyzing the literature, this study discovers the evolution and taxonomy of DT, other technologies essential for its deployment, its proactive role in implementing CE and SDGs, and some challenges. Key findings of case studies reveal the current trajectory of employing DT with other digital products, upholding the CE practices within the bounds of the SDGs in Irish companies. In conclusion, DT is a conceivable means for advancing CE solutions and attaining SDGs towards social, economic, and environmental sustainability. The implications of this study are both theoretically and practically significant, encouraging industrialists and academia to adopt DT. It will help scholars gain a thorough understanding and guide industrialists to downsize their carbon footprint and waste, accomplishing SDGs. It will inspire managers with DT-driven information for decision-making and facilitate government and policymakers to collaborate in designing essential policies. Graphical Abstract

Non-leguminous green manures improve labile phosphorus availability and crop yield in agroecosystems: A global meta-analysis - Adnan Anwar Khan; Imran Azeem; Jing Hui; Yupei Chen; Yuqi Yuan; Tahir Shah; Muhammad Adeel; Noman Shakoor; Rana Muhammad Ammar Asghar; Weidong Cao; Dabin Zhang; Yajun Gao (Soil and Tillage Research, 2025)

Investigating the interaction of breed and seasonality on milk quality parameters in different dairy cow breeds - Hafiz Muhammad Jawad Saleem; Qamar Abbas Syed; Sumayah Abbas; Muhammad Azeem; Saba Anwar; Ali Hassan (Food and Humanity, 2025)

Amelioration of pain and adjuvant-induced arthritis by syringic acid via modulation of behavioral parameters and inflammatory mediators i.e. TNF-α, Interleukins, MCP-1, NF-kB and COX-2 - Noviara Saleem; Syed Atif Raza; Alamgeer; Muhammad Khalil-ur-Rehman; Rukhsana Anwar; Abrar Ahmed; Hafiz Muhammad Irfan (Inflammopharmacology, 2025)

Development and exploration of casein-based nano-encapsulation of mangiferin for cow milk allergy management and immunomodulation - Muhammad Junaid Anwar; Aneela Hameed; Muhammad Usman Khan; Aimen Mazhar; Hafiz Muhammad Irfan Manzoor (Food Bioscience, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Organic and inorganic amendments improved the morpho-physiological and nutritional status of moringa (Moringa oleifera) genotypes - Madeeha kauser; Ejaz Ahmad Waraich; Hafeez ur Rehman; Muhammad Anwar ul Haq (Acta Physiologiae Plantarum, 2025)

Evaluating the pest control efficiency of wheat storage bags and polypropylene liners against Trogoderma granarium and Tribolium castaneum - Somair Razaq; Mussaddiq Hussain; Muhammad Waqar Hassan; Ghulam Sarwar; Tauseef Anwar; Huma Qureshi; Muhammad Tahir Naseem; Mansour I. Almansour; Sulaiman Ali Alharbi (International Journal of Tropical Insect Science, 2025)

Impact of urea-molasses treated wheat straw levels in total mixed rations on growth and nutrient digestibility in Azikheli buffalo calves - Haroon Ur Rashid; Taimoor Khan; Anwar Ali Turi; Muhammad Abbas; Kalim Ullah; Isa Fusaro; Giovanni Buonaiuto; Damiano Cavallini (Tropical Animal Health and Production, 2025)
This study investigates the impact of urea molasses-treated wheat straw on growth performance and nutrient digestibility in Azikheli buffalo male calves. A longitudinal experiment was conducted on sixteen calves, randomly assigned to four experimental dietary treatments ( n = 4 per group). The experimental diets included a control group (U0) with untreated wheat straw and three groups where urea molasses-treated wheat straw replaced 33% (U33), 66% (U66), or 100% (U100) of the straw in the total mixed ration. Results indicated that increasing the proportion of urea-treated wheat straw from 0 to 100% led to significant improvements in dry matter intake (from 2931 to 4034 g/day) and organic matter intake (from 2596 to 3623 g/day). Digestibility of dry matter, organic matter, crude protein, and crude fiber also followed an increasing trend, reaching 77.42%, 81.21%, 87.10%, and 60.22%, respectively, at the highest urea-treated wheat straw level. Furthermore, weight gain was significantly greater in calves fed 100% urea-treated wheat straw, followed by those in the U66, U33, and U0 groups. Feed conversion efficiency improved substantially in the U100 and U66 groups than U33 and U0. These findings suggest that incorporating higher levels of UMTWS in total mixed rations enhances nutrient digestibility, promoting superior growth performance and feed efficiency in Azikheli buffalo calves.

Chemically Degraded Soil: Strategies for Mitigating its Toxicity and Enhancing Sustainable Crop Production - Mavadat Hussain Alvi; Habib Ali; Kamran Haider; Adeel Hussain Chughtai; Muhammad Abdullah; Seema Batool; Shahid Rasool; Rana Noman Anwar; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Isolation and characterization of Aspergillus oryzae from Withania coagulans rhizosphere: metabolite profiling and bioactivity assessment - Sidra Farooq; Asif Mehmood; Nasir Ali; Muhammad Irshad; Anwar Hussain; Naeem Khan (Journal of Plant Biochemistry and Biotechnology, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Physicochemical profiling and health risk evaluation of effluents from textile industries: insights from Faisalabad, Pakistan - Hina Sattar; Muhammad Anwar-ul-Haq; Humera Aziz; Umair Riaz; Ahmad Mahmood; Muhammad Rizwan; Munaza Naseem; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Toxicology and Environmental Health Sciences, 2025)

Photovoltaic module efficiency enhancement system by novel cooling techniques: Effect of phase change material and fins - Saad Saeed; Abid Hussain; Imran Ali; Hanzla Shahid; Muhammad Anwar; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2025)

Tailoring the electrochemical performance of rods-like Co-MOF: Fe-derived Co3O4: Fe electrodes for supercapacitor applications - Maryam Shah; Sonadia; Zoya Iqbal; Anwar Ul-Hamid; Muhammad Umair Mushtaq; Fahad Azad (Fuel, 2025)

Smartphone-integrated inkjet-printed paper sensor and UV/Vis spectrophotometric method for on-site detection of As3+ and L-cysteine in food samples using novel AMTPP-functionalized silver nanoparticles - Sufian Rasheed; Kashif Hussain; Shan Arif; Abdul Rehman Umar; Syeda Bushra Anwar; Haji Muhammad; Kousar Yasmeen; Mustafa Tuzen; Muhammad Raza Shah (Food Chemistry, 2025)

Cooling load reduction strategies for community worship place towards attaining sustainability: a life cycle cost perspective - Fatima Anwar; Muhammad Sohail Anwar Malik; Mughees Aslam; Rai Waqas Azfar Khan (The International Journal of Life Cycle Assessment, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

MXenes: Transforming advanced materials through electrochemical reduction reactions – Opportunities and challenges - Tahir Rasheed; Sameera Shafi; Muhammad Tuoqeer Anwar; Rabia Ahmad; Muhammad Sheraz Ahmad; Muhammad Usman; Khaled Fahmi Fawy (Chemical Engineering Journal, 2025)

Particle size of wheat straw from genetically improved wheat affects the production performance and feeding behavior of Sahiwal cows - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Muhammad Qamar Bilal; Muhammad Riaz; Muhammad Farooq Khalid; Zia-Ur-Rehman; Urooj Anwar; Riaz Mustafa; Waseem Abbas; Umar Farooq (Tropical Animal Health and Production, 2025)

Mitigation of salinity stress in sunflower plants (Helianthus annuus L.) through topical application of salicylic acid and silver nanoparticles - Muhammad Shahbaz; Tauseef Anwar; Sammer Fatima; Nilgün Onursal; Huma Qureshi; Waseem Akhtar Qureshi; Naimat Ullah; Walid Soufan; Wajid Zaman (Physiology and Molecular Biology of Plants, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Fluorescence Analysis of Antibacterial Activity of ZnO/TiO2 Electrospun Nanofibers: A Molecular Approach to Reveals the Insights of Physiochemical Interactions of Materials with Bacteria - Ali Hassan; Shahzad Anwar; Rashad Rashid; Rafaqat Ali Khan; Saba Ibrahim; Bisma Khanam; Attaullah Shah; Muhammad Raffi (Journal of Fluorescence, 2024)

Retraction Note: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2024)

Bioaugmentation of a novel bacterial consortium in cotton-planted soil for lambda-cyhalothrin degradation - Samina ANWAR; Anusha LIAQAT; Asma MUNIR; Muhammad F. ASHRAF; Samina IQBAL (Pedosphere, 2024)

Environmental impacts of the billion tree Tsunami project in Khyber Pakhtunkhwa on the dynamics of Agro-Meteorological Droughts - Khalil Ur Rahman; Deqiang Mao; Nuaman Ejaz; Quoc Bao Pham; Anwar Hussain; Meriame Mohajane; Muhammad Ali; Songhao Shang (Journal of Hydrology, 2024)

Assessing the combined impacts of microplastics and nickel oxide nanomaterials on soybean growth and nitrogen fixation potential - Imran Azeem; Quanlong Wang; Muhammad Adeel; Noman Shakoor; Muhammad Zain; Adnan Anwar khan; Yuanbo Li; Kamran Azeem; Muhammad Nadeem; Guikai Zhu; Rui Yukui (Journal of Hazardous Materials, 2024)

Nutraceutical tablets: Manufacturing processes, quality assurance, and effects on human health - Muhammad Faisal Manzoor; Sakhawat Riaz; Deepak Kumar Verma; Muhammad Waseem; Gulden Goksen; Anwar Ali; Xin-An Zeng (Food Research International, 2024)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Role of exogenous silica fertilization and genotype selection in attenuating oxidative and osmotic stress in wheat (Triticum aestivum L.) under water deficit conditions - Muhammad Anwar ul Haq; Muhammad Nadeem; Munaza Naseem; Ghulam Hasan Abbasi; Muhammad Ali; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Tayyab Mehmood; Muhammad Awais; Rizwan Ullah; Tasawar Ali (Plant and Soil, 2024)

Bridging drug discovery through hierarchical subtractive genomics against asd, trpG, and secY of pneumonia causing MDR Staphylococcus aureus - Ayesha Wisal; Nida Saeed; Muhammad Aurongzeb; Muhammad Shafique; Saman Sohail; Waheed Anwar; Zarrin Basharat; Muhammad Irfan; Asad Ullah; Syed S. Hassan (Molecular Genetics and Genomics, 2024)

Comparative assessment of pantothenic, aspartic, ascorbic and tartaric acids assisted Pb-phytoextraction by sunflower (Helianthus annuus L.) - Asif Ghafoor; Fahad Shafiq; Sumera Anwar; Lixin Zhang; Muhammad Ashraf (BioMetals, 2024)

Reliable attitude control integrating reaction wheels and embedded asymmetric magnetorquers for detumbling CubeSats - Shoaib Ahmed Khan; Zou Tao; Shah Fahad; Muhammad Salman; Mustafa Tahir; Anwar Ali (Advances in Space Research, 2024)

Monitoring groundwater vulnerability for sustainable water resource management: A DRASTIC-based comparative assessment in a newly township area of Bangladesh - Muhammad Anwar Iqbal; Mohammed Abdus Salam; Md Nur-E-Alam; Nusrat Jahan Rubaida; Hafizur Rahman; Mohammed Faruque Uddin (Groundwater for Sustainable Development, 2024)

Microfluidic devices for the isolation and label-free identification of circulating tumor cells - Muhammad Anwar; Nuno M. Reis; Chi Zhang; Adil Khan; Kashif Ali Kalhoro; Atiq Ur Rehman; Yanke Zhang; Zhengchun Liu (Chemical Engineering Journal, 2024)

Microsatellite Markers & Mitochondrial D-Loop Based Phylogenetic And Diversity Analysis In Gabrali Cattle - Farhad Ali; Syed Muhammad Suhail; Farhan Anwar Khan; Ijaz Ahmad (Tropical Animal Health and Production, 2024)

Evaluating the biological activity of rolB-transgenic Nicotiana tabacum plants using phytochemical and pharmacological approaches - Afshan Anwar; Shabana Haneef; Hammad Ismail; Muhammad Zeeshan Bhatti; Nazif Ullah; Iram Murtaza; Bushra Mirza (Plant Biosystems, 2024)

Antibacterial Efficacy of Tryptophan Coordinated Silver Nanoparticles Against E. coli: Spectroscopic and Microscopic Evaluation of Bacterial Cell Death - Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Uzma Aziz; Bisma Khanam; Muhammad Zakria; Muhammad Raffi (Journal of Fluorescence, 2024)

Assessing Trace Metal-Based Human Health Risks for Commonly Used Body Soaps in Bangladesh - Ashraful Hoque; Taznova Anwar Tanbi; Nakshi Saha; Sabbir Howlader; Nobonita Sarker; Aminul Islam Chowdhury; Amitava Bandyopadhyay; Shahidul Islam; Muhammad Abu Bakar; Nur E. Alam; Ashok Kumar Chakraborty; Sumon Ganguli (Biological Trace Element Research, 2024)

Health risk assessment of bread wheat grown under cadmium and nickel stress and impact of silicic acid application on its growth, physiology, and metal uptake - Alina Shafiq; Muhammad Emmad Munawar; Muhammad Nadeem; Asia Khan; Ghulam Hasan Abbasi; Muhammad Anwar ul Haq; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Control efficacy of isolates of Aspergillus nidulans and Aspergillus fumigatus against three destructive insect pests of stored grain - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal; Waheed Anwar; Muhammad Ali (Journal of Stored Products Research, 2024)

Characterization and Induction of Biochar Induced Capsicum annumm Defense Against Bacterial Wilt - Muhammad Taqqi Abbas; Tehmina Anjum; Waheed Anwar; Muhammad Khurshid; Adnan Akhter (Journal of Soil Science and Plant Nutrition, 2024)

Mapping the global spatial dynamics: renewable energy’s impact on air pollution spillovers in high-contaminant regions - Syed Jaffar Abbas; Asim Iqbal; Muhammad Munawar Hussain; Aftab Anwar (Environment, Development and Sustainability, 2024)

Effects of Withania somnifera (L.) Dunal in acute pulmonary pathophysiology in a rat model of smoke-induced lung injury and role of IRS-1 and SOX-2 - Sana Saleem; Imran Mukhtar; Hanan Y. Aati; Humaira Muzaffar; Haseeb Anwar; Musaddique Hussain; Maqsood Ahmad; Muhammad Umair; Kashif-ur-Rehman Khan (South African Journal of Botany, 2024)

Phytoremediation of Arsenic (As) in rice plants, mediated by strain IU31 through antioxidant responses and phytohormones synthesis - Ihsan Ullah; Yasir Anwar; Muhammad Faisal Siddiqui; Nadiah Alsulami; Raza Ullah (Environmental Pollution, 2024)

Geospatial identification of possible rainwater harvesting locations within a high-altitude Gilgit River basin, Pakistan - Madiha Asif; Muhammad Yaseen; Syed Umair Shahid; Yasir Latif; Salma Anwar; Sohail Abbas (Theoretical and Applied Climatology, 2024)
The management of water resources is no longer an option but a necessity especially in countries with a high rate of population growth like Pakistan. Pakistan has a high-water scarcity, an extremely varying topography, and is also one of the countries encountering the problem of climate change. Therefore, prudent utilization of available water resources is a matter in the plains of Pakistan as in its high-altitude regions. Instead of wasting water which is a valuable resource, rainwater harvesting is a way of saving rainwater as an alternative source of fresh water for better use. The aim of this study was to search for potential rainwater-harvesting areas in a high-altitude Gilgit River basin. This research employed the SCS-CN technique in estimating surface runoff in the GIS environment. The geospatial study used four input parameters: slope of the land, land covers, surface runoff and drainage density. The research concluded that some lands, especially those that are deserted in dry area and agricultural lands, can serve as the sites of rainwater harvesting, with only 4% of area that was highly suitable for the purpose. Nevertheless, 37% of the investigated area was shown as totally unviable for rainwater collection installations because of steep slopes and substantial volume of snow. Simultaneously, the rainwater storage design solutions suggested were check dam, percolation tank, and agricultural ponds with the area of 3.5%, 1%, and 0.75% of the given land area, respectively, for rainwater harvesting. The locations of potential catchment and planned rainwater harvesting structures would assist the local authorities and the policy makers to provide plans and design on the construction of water storages and also the optimization of water use.

Analysing spatiotemporal drought patterns in Punjab Province, Pakistan, utilizing SPI and SPEI - Anwar Hussain; Muhammad Suliman; Firdos Khan (Theoretical and Applied Climatology, 2024)

Chemical analogue based drug design for cancer treatment targeting PI3K: integrating machine learning and molecular modeling - Mohammed A. Bazuhair; Anwar A. Alghamdi; Othman Baothman; Muhammad Afzal; Sami I. Alzarea; Faisal Imam; Ehssan Moglad; Hisham N. Altayb (Molecular Diversity, 2024)

Asymmetric effects of high-tech industry and presence of pollution-haven hypothesis in APEC countries: fresh evidence with panel quantile regression - Qasim Raza Khan; Ahsan Anwar; Tufail Muhammad; Noorulhaq Ghafoori; Mushtaq Ahmad (Clean Technologies and Environmental Policy, 2024)

Silicon oxide nanoparticle mitigated the vanadium toxicity in Cucumber (Cucumis sativus L.) - Muhammad Mohsin Altaf; Sahrish Ashraf; Muhammad Qaisar Naeem Khan; Sibgha Noreen; Muhammad Anwar; Rafa Almeer; Rattandeep Singh; Atique ur Rehman (South African Journal of Botany, 2024)

Synergistic cytotoxicity effect by combination of N-hexane fraction of the herbs (Peperomia pellucida) with doxorubicin against breast cancer cells (MCF-7) - Marissa Angelina; Marya Salfia Khoerunisah; Kasiyati; Alfian Mahardika Forentin; Muhammad Anwar Djaelani (South African Journal of Botany, 2024)

Assessing the impact of natural capital and innovation on sustainable development in developing countries - Muhammad Asghar; Nidhaleddine Ben Cheikh; Ahmed Imran Hunjra; Anwar Khan (Journal of Cleaner Production, 2024)

Techno-economic and performance assessment of a hybrid fuel cell-based combined heat and power system for dairy industry - Kashif Najeeb; Abdul Haseeb Tariq; Muhammad Hassan; Mustafa Anwar; Ali Bahadar; Syed Ali Abbas Kazmi; Muhammad Yousif (Environment, Development and Sustainability, 2024)

Development and validation of an indirect ELISA for the serodiagnosis of contagious caprine pleuropneumonia in goats - Hayatullah Khan; Farhan Anwar Khan; Umer Sadique; Ijaz Ahmad; Muhammad Saeed; Faisal Ahmad; Faiz Ur Rehman; Hanif Ur Rahman (Small Ruminant Research, 2024)

Role of resources rent, research and development, and information and communication technologies on CO2 emissions in BRICS economies - Ruikun Zhu; Qi Xu; Xia Xiqiang; Muhammad Sibt-e-Ali; Muhammad Waqas; Irfan Ullah; Ahsan Anwar (Resources Policy, 2024)

Towards artificial intelligence empowered performance enhancement of EDM process using nano-graphene mixed bio-dielectric supporting the carbon neutrality and sustainable development - Kashif Ishfaq; Muhammad Asad; Waqar Muhammad Ashraf; Muhammad Sana; Saqib Anwar; Wei Zhang; Vivek Dua (Journal of Cleaner Production, 2024)

Spatial distribution of heavy metal abundance at distance gradients of roadside agricultural soil from the busiest highway in Bangladesh: A multi-index integration approach - Md. Saydul Islam; Md. Nur-E-Alam; Muhammad Anwar Iqbal; Md. Badiuzzaman Khan; Shamim Al Mamun; Md. Yunus Miah; Md. Rasheduzzaman; S. Appalasamy; Mohammed Abdus Salam (Environmental Research, 2024)

Molecular mechanisms of morphine tolerance and dependence; novel insights and future perspectives - Ismail Badshah; Maira Anwar; Babar Murtaza; Muhammad Imran Khan (Molecular and Cellular Biochemistry, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Multiple Transgenic Strategies Positively Regulate Cold-Induced Sweetening in Low Temperature Stored Potato Tubers - Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Shazia Shafique; Nusrat Jahan; Muhammad Umar Bhatti; Rida Khalid; Ayman Naeem; Qamar Abbas; Sobiya Shafique; Bushra Tabassum (Potato Research, 2024)

Treatment of marble industry wastewater by Brassica napus (L.) under oxalic acid amendment: efficacy as fodder and carcinogenic risk assessment - Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Ramzan Anwar; Mujahid Farid; Wajiha Sarfraz; Muhammad Zubair; Zaki Ul Zaman Asam; Mohsin Abbas; Muhammad Rizwan (Environmental Science and Pollution Research, 2024)

Evaluation of the potentials of rice varieties and water management practices for reducing human health risks associated with polluted river water irrigated rice in Bangladesh - Masahiro Tokumura; Jumpei Miyazaki; Mahmud Hossain; Anwar Hossain; Mohammad Raknuzzaman; Qi Wang; Yuichi Miyake; Takashi Amagai; Shigeki Masunaga; Shofiqul Islam; Muhammad Rafiqul Islam; Masakazu Makino (Science of The Total Environment, 2024)

Association of polymorphism in the promotor area of the caprine BMPR1B gene with litter size and body measurement traits in Damani goats - Inayat Ullah; Rajwali Khan; Syed Muhammad Suhail; Ijaz Ahmad; Farhan Anwar Khan; Muhammad Shoaib; Kamran Farid; Amel Ayari-Akkari; Ekhlas Ali Morfeine (Tropical Animal Health and Production, 2024)

New bisbenzylisoquinoline alkaloid, isolation and structure elucidation from Cocculus pendulus - Shaikh Ziauddin Sultani; Muhammad Aijaz Anwar; Muhammad Shahab Alam (Natural Product Research, 2024)

Predictors of quitting smoking behavior: evidence from Pakistan - Assad Ullah Khan; Anwar Shah; Muhammad Tariq Majeed; Sareer Ahmad (Environmental Science and Pollution Research, 2024)

Synergistic transformation: Kinetic and thermodynamic evaluation of co-pyrolysis for low-rank bituminous coal and polyurethane foam waste - Zaid Mohammad Banyhani; Waqar Ul Habib Khan; Hala H. Abd El-Gawad; Mustafa Anwar; Asif Hussain Khoja; Muhammad Hassan; Rabia Liaquat; Zeinhom M. El-Bahy (Process Safety and Environmental Protection, 2024)

Potential of Capparis decidua plant and eggshell composite adsorbent for effective removal of anionic dyes from aqueous medium - Ghulam Mujtaba; Abdul Hai; Mansoor Ul Hassan Shah; Asad Ullah; Yasir Anwar; Furqan Shah; Muhammad Daud; Afzal Hussain; Faheem Ahmed; Fawzi Banat (Environmental Research, 2024)

Modelling photoperiod in enhancing hydrogen production from Chlorella vulgaris sp. while bioremediating ammonium and organic pollutants in municipal wastewater - Fatima Musa Ardo; Kuan Shiong Khoo; Mohamad Zulfadhli Ahmad Sobri; Uganeeswary Suparmaniam; Baranitharan Ethiraj; Aliya Fathima Anwar; Sze Mun Lam; Jin Chung Sin; Muhammad Kashif Shahid; Sabah Ansar; Anita Ramli; Jun Wei Lim (Environmental Pollution, 2024)

Modeling spatial distribution of earthquake epicenters using inhomogeneous Log-Gaussian Cox point process - Salma Anwar; Muhammad Yaseen; Muhammad Yaseen; Yasir Latif (Modeling Earth Systems and Environment, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Microorganism-mediated biodegradation for effective management and/or removal of micro-plastics from the environment: a comprehensive review - Hassan Zahid; Nimra Afzal; Muhammad Maaz Arif; Mahnoor Zahid; Samia Nawab; Malik Muhammad Qasim; Farhat Naseem Alvi; Sumbal Nazir; Ishrat Perveen; Naaz Abbas; Yasar Saleem; Sania Mazhar; et al. (Archives of Microbiology, 2024)

Self-assembled micelles loaded with itraconazole as anti-Acanthamoeba nano-formulation - Komal Rao; Muhammad Abdullah; Usman Ahmed; Hashi Isse Wehelie; Muhammad Raza Shah; Ruqaiyyah Siddiqui; Naveed A. Khan; Bader S. Alawfi; Ayaz Anwar (Archives of Microbiology, 2024)

Energy, economic and environmental (3E) analyses of solar photovoltaic and fuel cell based hybrid energy system for a developing country: a worldwide approach to sustainable energy - Maham Fazal; Abdul Kashif Janjua; Mustafa Anwar; Muhammad Hassan; Sehar Shakir; Ali Bahadar (Environment, Development and Sustainability, 2024)

Linking energy-based circularity with environment in high-income economies - Muhammad Usman; Syed Asif Ali Naqvi; Sofia Anwar; Abdul Majeed Nadeem (Environmental Science and Pollution Research, 2024)

Reduced toxic effects of nano‑copper sulfate in comparison of bulk CuSO4 on biochemical parameters in the Rohu (Labeo rohita) - Azka Anwar; Fahim Ullah Khan; Waqar Younas; Muhib Zaman; Muhammad Noorullah; Li'ang Li; Amina Zuberi; Youji Wang (Toxicology in Vitro, 2024)

Potential application of 2D nano-layered MXene in analysing and remediating endocrine disruptor compounds and heavy metals in water - Muhammad Nur’ Hafiz Rozaini; Kuan Shiong Khoo; Muhammad Amirul Aizat Mohd Abdah; Baranitharan Ethiraj; Mohammad Mahtab Alam; Aliya Fathima Anwar; Normawati M. Yunus; Chin Seng Liew; Jun Wei Lim; Chii-Dong Ho; Woei-Yenn Tong (Environmental Geochemistry and Health, 2024)

Does financial sector is helpful for curbing carbon emissions through the investment in green energy projects: evidence from MMQR approach - Muhammad Farhan Basheer; Ahsan Anwar; Saria Ghulam Hassan; Ibrahim Tawfeeq Alsedrah; Phan The Cong (Clean Technologies and Environmental Policy, 2024)

Sustainable electric discharge machining using alumina-mixed deionized water as dielectric: Process modelling by artificial neural networks underpinning net-zero from industry - Muhammad Sana; Muhammad Asad; Muhammad Umar Farooq; Saqib Anwar; Muhammad Talha (Journal of Cleaner Production, 2024)

RETRACTED: Effects of vermicompost on soil microbiological properties in lettuce rhizosphere: An environmentally friendly approach for sustainable green future - Muhammad Danish Toor; Ridvan kizilkaya; Aneela Anwar; Lyubka Koleva; Gaber E. Eldesoky (Environmental Research, 2024)

A comparison of experimental and computational methods for circular footing response on lime-treated geotextile reinforced silty sand - Syed Md Yousuf; Mehboob Anwar Khan; Syed Muhammad Ibrahim; Anil Kumar Sharma; Furquan Ahmad; Pramod Kumar (Modeling Earth Systems and Environment, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Phytoremediation of heavy metals spiked soil by Celosia argentea L.: effect on plant growth and metal stabilization - Umer Hussain; Rabia Afza; Iram Gul; Muhammad Anwar Sajad; Ghulam Mujtaba Shah; Zahir Muhammad; Shujaul Mulk Khan (Environmental Science and Pollution Research, 2024)

Physiological and biochemical effects of biochar nanoparticles on spinach exposed to salinity and drought stresses - Aimun Rasheed; Sumera Anwar; Fahad Shafiq; Zaib-un-Nisa; Shahbaz Khan; Muhammad Ashraf (Environmental Science and Pollution Research, 2024)

Analyzing employees’ green behavioral intention in the hospitality industry: a multilevel model - Bilal Khalid; Khurram Shahzad; Muhammad Usman Anwar Baig (Environment, Development and Sustainability, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Effects of seasonal temperature regimes: Does Cyprinus carpio act as a health hazard during the construction of Suki Kinari hydropower project on Kunhar River in Pakistan? - Shan-e-hyder Soomro; Xiaotao Shi; Jiali Guo; Shaista Jalbani; Muhammad Asad; Muhammad Imran Anwar; Caihong Hu; Senfan Ke; Yanqin Bai; Yuanyang Wang (Science of The Total Environment, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Systematic review and meta-analysis of the potential threats to respiratory health from microbial Bioaerosol exposures - Muhammad Anwar Iqbal; Sadia Afrin Siddiqua; Mohammad Omar Faruk; Abu Reza Md. Towfiqul Islam; Mohammed Abdus Salam (Environmental Pollution, 2024)

Black carbon emissions inventory and scenario analysis for Pakistan - Kaleem Anwar Mir; Pallav Purohit; Muhammad Ijaz; Zaeem Bin Babar; Shahbaz Mehmood (Environmental Pollution, 2024)

Impact of transportation infrastructure and urbanization on environmental pollution: evidence from novel wavelet quantile correlation approach - Muhammad Usman Malik; Zia ur Rehman; Arshian Sharif; Ahsan Anwar (Environmental Science and Pollution Research, 2023)

Smartphone-integrated colorimetric and microfluidic paper-based analytical devices for the trace-level detection of permethrin - Sufian Rasheed; Muhammad Anwar ul Haq; Naseer Ahmad; Sirajuddin; Dilshad Hussain (Food Chemistry, 2023)

Future prospects of biomass waste as renewable source of energy in Pakistan: A mini review - Waqas Ahmad; Jan Nisar; Farooq Anwar; Faisal Muhammad (Bioresource Technology Reports, 2023)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Polymorphism and association study of lactoferrin (LF) gene with milk yield, milk composition, and somatic cell count in Beetal goats - Lionel Kinkpe; Rajwali Khan; Syed Muhammad Suhail; Ijaz Ahmad; Farhan Anwar Khan; Amel Ayari-Akkari; Sazada Siddiqui (Tropical Animal Health and Production, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Attenuation of CFA-induced arthritis through regulation of inflammatory cytokines and antioxidant mechanisms by Solanum nigrum L. leaves extracts - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Mobasher Ahmad; Muhammad Ihsan Ullah; Shahzad Kamran (Inflammopharmacology, 2023)

Curative potential of Populus ciliata Wall ex. Royle extract against adjuvant-induced arthritis and peripheral neuropathy in Wistar rats - Amna Tahir; Muhammad Furqan Akhtar; Ammara Saleem; Muhammad Naveed; Basiru Olaitan Ajiboye; Fareeha Anwar; Aslam Khan (Inflammopharmacology, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Mesoporous Cr2O3/MWCNTs/PANI nanocomposite as a high performance anode material for rechargeable lithium ion batteries - Laraib Kiran; Mehmet Kadri Aydınol; Syed Sakhawat Shah; Aneela Anwar; Syed Mustansar Abbas; Doruk Bahtiyar; Muhammad Siddiq; Abdul Rehman; Mohamed Ouladsmane; Muhammad Imran Shahzad (Fuel, 2023)

CIMCA: Infusing computational intelligence in multi-criteria analysis to assess groundwater potential for recharge - Rashed Uz Zzaman; Muhammad Ali Nayeem; Sara Nowreen; Imran Hossain Newton; AKM Saiful Islam; Anwar Zahid; M. Sohel Rahman (Environmental Modelling & Software, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Fluorescence Spectroscopy for the Assessment of Microbial Load in UVC Treated Water - Sana Imtiaz; Shahzad Anwar; Laiq Zada; Hina Ali; M. Saeed Khurram; Azhar Saeed; Muhammad Saleem (Journal of Fluorescence, 2023)

Nexus between biomass energy, economic growth, and ecological footprints: empirical investigation from belt and road initiative economies - Muhammad Awais Anwar; Noman Arshed; Aviral Kumar Tiwari (Environmental Science and Pollution Research, 2023)

Differential accumulation pattern of cadmium in plant parts of pea varieties in response to varying cadmium levels - Khurram Ziaf; Hafiz Muhammad Talha; Muhammad Awais Ghani; Iftikhar Ahmad; Raheel Anwar; Basharat Ali; Yasir Majeed; Amir Shakeel; Mudassar Iqbal; Abbu Zaid (South African Journal of Botany, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Impact of graded levels of coated calcium butyrate on growth performance and serological indices during pre-weaning stage in Holstein calves - Abdur Rahman; Muhammad Furhan Arshad; Shah Nawaz; Zafar Hayat; Syed Ehtisham ul Haque; Saima Saima; Akhtar Rasool Asif; Muawuz Ijaz; Muhammad Zeeshan Anwar (Tropical Animal Health and Production, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Retraction Note: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2023)

Natural occurrence of fungal species on the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae), in Punjab, Pakistan - Tiyyabah Khan; Hafiz Azhar Ali Khan; Waheed Anwar; Muhammad Rizwan Khan; Muhammad Umer (International Journal of Tropical Insect Science, 2023)

The deteriorating effects of cadmium accumulation on the yield and quality of maize crops - Naila Shah; Muhammad Irshad; Anwar Hussain; Asif Mehmood; Waheed Murad; Muhammad Qadir; Muhammad Awais; Mohib Shah; Naeem Khan (South African Journal of Botany, 2023)

Manufacturing energy and environmental evaluation of metallic sheets reshaping based on theoretical models and cradle-to-gate assessment - Anwar Algamal; Muhammad Ali Ablat; Majed Ali; Abdalmageed Almotari; Ala Qattawi (Journal of Cleaner Production, 2023)

RETRACTED: Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2023)

Role of Exogenous Osmolyte Supplementation in Ameliorating Osmotic and Oxidative Stress and Promoting Growth in Salinity-Stressed Soybean Genotypes - Muhammad Anwar-ul-Haq; Irfan Iftikhar; Javaid Akhtar; Muhammad Maqsood (Journal of Soil Science and Plant Nutrition, 2023)

Vector indices and metrological factors associated with dengue fever outbreak in Punjab, Pakistan - Muhammad Irfan Akram; Waseem Akram; Muhammad Asif Qayyoum; Adeela Anwar Rana; Muhammad Yasin; Bushra Saddiq (Environment, Development and Sustainability, 2023)

Effect of green Fe2O3 nanoparticles in controlling Fusarium fruit rot disease of loquat in Pakistan - Faryal Niazi; Musrat Ali; Urooj Haroon; Farhana; Asif Kamal; Taskeen Rashid; Fareeha Anwar; Rabia Nawab; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Brazilian Journal of Microbiology, 2023)

An insight into the hepatoprotective role of Velpatasvir and Sofosbuvir per se and in combination against carbon tetrachloride-induced hepatic fibrosis in rats - Sadaf Yasmeen; Aslam Khan; Fareeha Anwar; Muhammad Furqan Akhtar; Sidra Yasmeen; Shafeeq Ali Shah (Environmental Science and Pollution Research, 2023)

Natural disasters, resilience-building, and risk: achieving sustainable cities and human settlements - Muhammad Tariq Iqbal Khan; Sofia Anwar; Samuel Asumadu Sarkodie; Muhammad Rizwan Yaseen; Abdul Majeed Nadeem; Qamar Ali (Natural Hazards, 2023)

A critical analysis of wastewater use in agriculture and associated health risks in Pakistan - Natasha; Muhammad Shahid; Sana Khalid; Behzad Murtaza; Hasnain Anwar; Ali Haidar Shah; Aneeza Sardar; Zunaira Shabbir; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2023)

Impact of green human resource management on green creativity in pharmaceutical companies: mediation role of green mindset - Muhammad Haseeb Shakil; Rana Nadir Idrees; Sadaf Ehsan; Waseem Anwar (Environmental Science and Pollution Research, 2023)

Attenuative effect of astilbin on polystyrene microplastics induced testicular damage: Biochemical, spermatological and histopathological-based evidences - Arooj Rizwan; Muhammad Umar Ijaz; Ali Hamza; Haseeb Anwar (Toxicology and Applied Pharmacology, 2023)

Effect of wind and solar energy production, and economic development on the environmental quality: Is this the solution to climate change? - Bilal Hussain; Syed Asif Ali Naqvi; Sofia Anwar; Muhammad Usman (Gondwana Research, 2023)

Selective anti-cancer activity against melanoma cells using 3- O -acetyl-β-boswellic acid-loaded 3D-Printed scaffold - Fatemeh Jamshidi-adegani; Saeid Vakilian; Sulaiman Al-Hashmi; Juhaina Al-Kindi; Najeeb Ur Rehman; Yaqeen Al-Sinani; Shokoofeh Ghaemi; Khurshid Alam; Muhammad U. Anwar; Rene Csuk; Ahmed Al-Harrasi (Natural Product Research, 2023)

Entrepreneurship and universities pedagogical perspectives and philosophies - Arman; Muhammad Ali Faisal; Saiful Anwar (The Social Science Journal, 2023)

Entropy-based grid approach for handling outliers: a case study to environmental monitoring data - Anwar Shah; Bahar Ali; Fazal Wahab; Inam Ullah; Kassian T. T. Amesho; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

Physiological effects of some engineered nanomaterials on radish (Raphanus sativus L.) intercropped with pea (Pisum sativum L.) - Mehr-un-Nisa; Fahad Shafiq; Sumera Anwar; Arslan Mahmood; Muhammad Iqbal; Kaleem Ullah; Muhammad Zulqarnain; Imtiaz Haider; Muhammad Ashraf; Lixin Zhang (Environmental Science and Pollution Research, 2023)

Frugal innovation as a source of sustainable entrepreneurship to tackle social and environmental challenges - Muhammad Shehryar Shahid; Mokter Hossain; Subhan Shahid; Tehreem Anwar (Journal of Cleaner Production, 2023)

Polyvinylpyrrolidone and chitosan-coated magnetite (Fe3O4) nanoparticles for catalytic and antimicrobial activity with molecular docking analysis - Ayesha; Muhammad Imran; Ali Haider; Iram Shahzadi; Sawaira Moeen; Anwar Ul-Hamid; Walid Nabgan; Anum Shahzadi; Thamraa Alshahrani; Muhammad Ikram (Journal of Environmental Chemical Engineering, 2023)

MoS2-TiO2 coated PVDF-based hollow fiber membranes for permeate flux enhancement in membrane distillation - Nurul Syazana Fuzil; Nur Hidayati Othman; Nur Hashimah Alias; Fauziah Marpani; Muhammad Shafiq Mat Shayuti; Munawar Zaman Shahruddin; Mohd Rizuan Mohd Razlan; Norazah Abd Rahman; Woei Jye Lau; Mohd Hafiz Dzarfan Othman; Ahmad Fauzi Ismail; Tutuk Djoko Kusworo; et al. (Journal of Environmental Chemical Engineering, 2023)

Interactive Effects of Soil and Foliar-Applied Nanobiochar on Growth, Metabolites, and Nutrient Composition in Daucus carota - Habiba Khaliq; Sumera Anwar; Fahad Shafiq; Muhammad Ashraf; Lixin Zhang; Imtiaz Haider; Shahbaz Khan (Journal of Plant Growth Regulation, 2023)

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

Cassia absus-mediated upregulation of IL-4, IL-10 and downregulation of IL-1β, IL-6, TNF- α, NF-κB, IFN-γ in CFA-induced arthritis model - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Afifa Noor; Muhammad Ihsan Ullah (Inflammopharmacology, 2023)

Physico-mechanical and petrographic analysis of the Margalla Hill Limestone, Islamabad, Lesser Himalaya, Pakistan - Basit Ali; Mumtaz Ali Khan; Muhammad Hanif; Masood Anwar; Beenish Ali; Mustafa Yar; Ijaz Ahmed (Carbonates and Evaporites, 2023)

Deciphering host–pathogen interaction during Streptomyces spp. infestation of potato - Ihtisham Ul Haq; Zahid Mukhtar; Muhammad Anwar-ul-Haq; Sana Liaqat (Archives of Microbiology, 2023)

The environmental cost of FDI and spatial implications of CO2 emissions in Sub-Saharan Africa - Syed Jaffar Abbas; Asim Iqbal; Muhammad Munawar Hussain; Aftab Anwar (Environmental Science and Pollution Research, 2023)

Transgenic maize inbred lines expressing high levels of Bacillus thuringiensis vegetative insecticidal protein (Vip3Aa86) offer effective control of maize stem borer (Chilo partellus) - Muhammad Umar Bhatti; Bushra Tabassum; Colin Berry; Anwar Khan; Uzma Qaisar; Ejaz Ali; Rida Khalid; Abdul Munim Farooq; Muhammad Tariq; Hasan Ayaz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

Influence of ionic cerium and cerium oxide nanoparticles on Zea mays seedlings grown with and without cadmium - Muhammad Ashar Ayub; Muhammad Zia ur Rehman; Hamaad Raza Ahmad; John-Paul Fox; Preston Clubb; Alan L. Wright; Muhammad Anwar-ul-Haq; Muhammad Nadeem; Cyren M. Rico; Lorenzo Rossi (Environmental Pollution, 2023)

Genetic polymorphism of Β-casein gene and its association with milk production and composition in Azi-Kheli buffalo - Khalid Khan; Syed Muhammad Suhail; Rajwali Khan; Ijaz Ahmed; Farhan Anwar Khan; Muhammad Jawad Khan (Tropical Animal Health and Production, 2023)

Therapeutic effect of gossypetin against paraquat-induced testicular damage in male rats: a histological and biochemical study - Shama Mustafa; Haseeb Anwar; Qurat ul Ain; Hussain Ahmed; Shabnoor Iqbal; Muhammad Umar Ijaz (Environmental Science and Pollution Research, 2023)

Eco-friendly bioactive β-caryophyllene/halloysite nanotubes loaded nanofibrous sheets for active food packaging - Azeem Ullah; Lei Sun; Fei-fei Wang; Hifza Nawaz; Kentaro Yamashita; Yingying Cai; Faiza Anwar; Muhammad Qamar Khan; Gopiraman Mayakrishnan; Ick Soo Kim (Food Packaging and Shelf Life, 2023)

The establishment of a rapid propagation system of the petiole of Hedera helix as explants - Pei Dongli; Muhammad Anwar; Song Yingying (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Higher order Gibbs point process modeling of 2005-Kashmir earthquakes - Salma Anwar; Muhammad Yaseen; Syed Amer Mahmood (Modeling Earth Systems and Environment, 2023)

The curative and mechanistic acumen of curcuminoids formulations against haloperidol induced Parkinson’s disease animal model - Uzma Saleem; Sundas Khalid; Zunera Chauhdary; Fareeha Anwar; Muhammad Ajmal Shah; Ifat Alsharif; Ahmad O. Babalghith; Rana O. Khayat; Aishah E. Albalawi; Tourki A. S. Baokbah; Maryam Farrukh; Celia Vargas-De-La-Cruz; et al. (Metabolic Brain Disease, 2023)

Corrigendum to “A review of the bioactive ingredients of berries and their applications in curing diseases” [Food Biosci. 44 (2021) 101407] - Akhunzada Bilawal; Muhammad Ishfaq; Munkh-Amgalan Gantumur; Abdul Qayum; Ruijie Shi; Saqib Ali Fazilani; Asif Anwar; Zhanmei Jiang; Juncai Hou (Food Bioscience, 2023)

Hexavalent chromium contamination in groundwater and its implication to human health: a Monte Carlo model approach in Indonesia - Ratna Dwi Puji Astuti; Anwar Mallongi; Ridwan Amiruddin; Muhammad Hatta; Annisa Utami Rauf (Sustainable Water Resources Management, 2023)

Techno-economic analysis of PV systems installed by using innovative strategies for smart sustainable agriculture farms - Yahya Aziz; Abdul Kashif Janjua; Muhammad Hassan; Mustafa Anwar; Saira Kanwal; Muhammad Yousif (Environment, Development and Sustainability, 2023)

Nitrogen-rich three-dimensional metal-organic framework microrods as an efficient electrocatalyst for oxygen evolution reaction and supercapacitor applications - Muhammad Imran Anwar; Sumaira Manzoor; Limin Ma; Muhammad Asad; Wenhua Zhang; Zahid Shafiq; Muhammad Naeem Ashiq; Guang Yang (Fuel, 2023)

Functionalized graphene oxide-zinc oxide hybrid material and its deployment for adsorptive removal of levofloxacin from aqueous media - Nimra Ismail; Muhammad Imran; Muhammad Ramzan; Ayesha Anwar; Ibrahim A. Alsafari; Muhammad Asgher; Hafiz M.N. Iqbal (Environmental Research, 2023)

Analyzing the impact of drought on agriculture: evidence from Pakistan using standardized precipitation evapotranspiration index - Anwar Hussain; Khan Zaib Jadoon; Khalil Ur Rahman; Songhao Shang; Muhammad Shahid; Nuaman Ejaz; Himayatullah Khan (Natural Hazards, 2023)

Natural remedies for Alzheimer’s disease: A systematic review of randomized controlled trials - Saara Ahmad; Saad Bilal Ahmed; Asra Khan; Muhammad Wasim; Saiqa Tabassum; Saida Haider; Fatima Ahmed; Zehra Batool; Saima Khaliq; Hamna Rafiq; Prashant Tikmani; Anwar-ul-Hassan Gilani (Metabolic Brain Disease, 2023)

Biomass energy consumption and sustainable development: empirical evidence from Asian economies - Naveed Asghar; Muhammad Tariq Majeed; Muhammad Waqas Khan; Awais Anwar (Environmental Science and Pollution Research, 2023)

Correction to: Assessment of soil-gas radon concentration over lithologies: a case study from district Karak, Khyber Pakhtunkhwa, Pakistan - Mumtaz Ali Khan; Nimat Ullah Khattak; Muhammad Hanif; Anwar Qadir (Environmental Monitoring and Assessment, 2023)

Assessment of soil-gas radon concentration over lithologies: a case study from district Karak, Khyber Pakhtunkhwa, Pakistan - Mumtaz Ali Khan; Nimat Ullah Khattak; Muhammad Hanif; Anwar Qadir (Environmental Monitoring and Assessment, 2023)

Genome wide association mapping of yield and various desirable agronomic traits in Rice - Muhammad Ashfaq; Abdul Rasheed; Muhammad Sajjad; Muhammad Ali; Bilal Rasool; Muhammad Arshad Javed; Sami Ul Allah; Shabnum Shaheen; Alia Anwar; Muhammad Shafiq Ahmad; Urooj Mubashar (Molecular Biology Reports, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Sedimentological and diagenetic analysis of Early Eocene Margalla Hill Limestone, Shahdara area, Islamabad, Pakistan: implications for reservoir potential - Haroon Aziz; Jabir Hussain; Muhammad Tariq; Muhsan Ehsan; Salman Khurshid; Saleem Khan; Waleed Anwar (Carbonates and Evaporites, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Estimation of economic, environmental, and social efficiency for sustainable development in G-8 and SAARC countries: a data envelopment analysis - Qamar Ali; Sofia Anwar; Muhammad Tariq Iqbal Khan; Muhammad Rizwan Yaseen; Muhammad Ashfaq (Environmental Science and Pollution Research, 2022)

An analysis of the environmental impacts of ethnic diversity, financial development, economic growth, urbanization, and energy consumption: fresh evidence from less-developed countries - Iftikhar Yasin; Sana Naseem; Muhammad Awais Anwar; Ghulam Rasool Madni; Haider Mahmood; Muntasir Murshed (Environmental Science and Pollution Research, 2022)

Correction to: Ecological footprint of your denim jeans: production knowledge and green consumerism - Fahad Asmi; Qingyu Zhang; Muhammad Azfar Anwar; Kristina Linke; Younes Ben Zaied (Sustainability Science, 2022)

Designing a clean environmental framework for Pakistan: analyzing the nonlinear impact of aggregate demand drivers on CO2 emissions - Muhammad Afaq Haider Jafri; Huizheng Liu; Sana Ullah; Muhammad Tariq Majeed; Shahzad Anwar; Sohaib Mustafa (Environmental Science and Pollution Research, 2022)

Variation in Vortex-Induced Vibration Phenomenon Due to Surface Roughness on Low- and High-Mass-Ratio Circular Cylinders: A Numerical Study - Muhammad Usman Anwar; Niaz Bahadur Khan; Muhammad Arshad; Adnan Munir; Muhammad Nasir Bashir; Mohammed Jameel; Muhammad Faisal Rehman; Sayed M. Eldin (Journal of Marine Science and Engineering, 2022)
Fluid–structure interaction has been widely studied in the last few decades due to its wide range of applications in engineering fields. This phenomenon plays an important design role, for example, in offshore risers, high slender buildings, chimney stacks and heat exchangers. The vortex shedding generated from a bluff body can induce high-amplitude oscillations, known as vortex-induced vibrations (VIVs). This study presents a numerical analysis to investigate the impact of surface roughness on VIV in the crossflow direction of a circular cylinder. The study also investigates the impact of surface roughness with variation in mass ratio from 2.4 to 11 at a high Reynolds number (Re) = 104 using Reynolds-averaged Navier–Stokes (RANS) equations. The study concludes that roughness on a cylinder results in a reduction in amplitude response. Furthermore, the lock-in region is narrower compared to that of a smooth cylinder, irrespective of the mass ratio. However, it is observed that the impact of surface roughness is more significant in high-mass-ratio cylinders where the lock-in region is more squeezed and shifted toward lower reduced velocities. Furthermore, the vortex mode beyond reduced velocities Ur = 5.84 and 7.52 was observed to be 2S for high and low mass ratios, respectively.

Correction to: Awareness regarding COVID‑19 and its effects on mental health among pre‑professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

Awareness regarding COVID-19 and its effects on mental health among pre-professional health sciences students at King Saud bin Abdulaziz University for health sciences in Riyadh and Jeddah, Saudi Arabia - Zackary Alghamdy; Ashwaq Alshahrani; Ismail Memon; Aslam Khan; Muhammad Anwar Khan; Yazeed Alrayani; Fulwah Alfawzan; Syed Faisal Zaidi (Environmental Science and Pollution Research, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Enhancement of chromate phytoremediation and soil reclamation potential of Brassica campestris L. by Aspergillus niger - Muhammad Qadir; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Nadia (Environmental Science and Pollution Research, 2022)

Characterization and Utilization of Cow Manure Biochar as Soil Amendment for the Management of Northern Corn Leaf Blight - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Adnan Akhter; Tehmina Bahar; Waheed Anwar; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2022)

Determination and detoxification of aflatoxin and ochratoxin in maize from different regions of Pakistan - Syed Wajih ul Hassan Shah Gillani; Yumna Sadef; Muhammad Imran; Hafiz Muhammad Fahad Raza; Aamir Ghani; Sumera Anwar; Muhammad Yasin Ashraf; Shabbir Hussain (Environmental Monitoring and Assessment, 2022)

Investigating feasible sites for multi-purpose small dams in Swat District of Khyber Pakhtunkhwa Province, Pakistan: socioeconomic and environmental considerations - Anwar Hussain; Khalil Ur Rahman; Muhammad Shahid; Sajjad Haider; Quoc Bao Pham; Nguyen Thi Thuy Linh; Saad Shauket Sammen (Environment, Development and Sustainability, 2022)

Ecological footprint of your denim jeans: production knowledge and green consumerism - Fahad Asmi; Qingyu Zhang; Muhammad Azfar Anwar; Kristina Linke; Younes Ben Zaied (Sustainability Science, 2022)

Production of a high molecular weight levan by Bacillus paralicheniformis, an industrially and agriculturally important isolate from the buffalo grass rhizosphere - Anam Nasir; Waqar Ahmad; Fazal Sattar; Iram Ashfaq; Stephen R. Lindemann; Ming-Hsu Chen; Wim Van den Ende; Ebru Toksoy Ӧner; Onur Kirtel; Shazia Khaliq; Muhammad A. Ghauri; Munir A. Anwar (Antonie van Leeuwenhoek, 2022)

Effect of Variation in the Mass Ratio on Vortex-Induced Vibration of a Circular Cylinder in Crossflow Direction at Reynold Number = 104: A Numerical Study Using RANS Model - Muhammad Usman Anwar; Maha M. A. Lashin; Niaz B. Khan; Adnan Munir; Mohammed Jameel; Riaz Muhammad; Kamel Guedri; Ahmed M. Galal (Journal of Marine Science and Engineering, 2022)
This study reports on the numerical analysis of the impact of mass ratio on the Vortex-Induced Vibration (VIV) phenomenon of an elastically rigid cylinder, oscillating freely in a crossflow direction. Reynolds-averaged Navier–Stokes (RANS) equations with (k-ω SST) model were used to analyze the flow behavior, amplitude ratio and vortex shedding patterns. The study was performed at constant Reynold number (Re) = 104 with reduced velocity (Ur) ranging from 2 to 14 and mass ratio (m*) of 2.4 and 11. The mass ratio was defined as the ratio between mass of the vibrating cylinder and mass of the fluid displaced. It was found that increasing the mass ratio from 2.4 to 11 resulted in decrease in amplitude response by 80%, 71% and 31% at initial branch, upper to lower transition region and lower branch, respectively. However, the amplitude in the upper branch decreased only 8% at high mass ratio. The peak amplitude observed in the present study was lower than previous experimental and DES results. However, the RANS k-ω SST well captured the vortex shedding modes of 2S, 2P, P + S, and 2T. In 2S mode, two single pairs of vortices were formed, whereas in 2P mode two pairs were generated in single oscillation. Similarly, P + S meant one pair and one individual vortex; whereas 2T mode meant two triplets of vortices generated in one oscillation. The study concluded that increase in mass ratio results in shortening of the lock-in region and decrease in amplitude response.

Effect of forage to concentrate ratio on growth performance and feeding behavior of Thalli lambs - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Karamo Jatta; Sajjad Khan; Muhammad Riaz; Qamar Bilal; Urooj Anwar; Sibtain Ahmad; Hassan Munir Bajwa; Fahd Rasul (Tropical Animal Health and Production, 2022)

Unraveling the role of China’s OFDI, institutional difference and B&R policy on energy efficiency: a meta-frontier super-SBM approach - Wasi Ul Hassan Shah; Gang Hao; Rizwana Yasmeen; Muhammad Abdul Kamal; Anwar Khan; Ihtsham Ul Haq Padda (Environmental Science and Pollution Research, 2022)

Sensitive and highly selective colorimetric biosensing of vitamin-C and vitamin-B1 by flavoring agent-based silver nanoparticles - Syeda Sumra Naqvi; Humera Anwar; Asma Siddiqui; Muhammad Raza Shah (JBIC Journal of Biological Inorganic Chemistry, 2022)

The role of infrastructure, socio-economic development, and food security to mitigate the loss of natural disasters - Muhammad Tariq Iqbal Khan; Sofia Anwar; Zahira Batool (Environmental Science and Pollution Research, 2022)

Ameliorative Effect of Silicic Acid and Silicates on Oxidative, Osmotic Stress, and Specific Ion Toxicity in Spring Wheat (Triticum aestivum L.) Genotypes - Muhammad Nadeem; Muhammad Anwar-ul-Haq; Muhammad Saqib; Muhammad Maqsood; Zhenli He (Journal of Soil Science and Plant Nutrition, 2022)

Influences of Long-term Crop Cultivation and Fertilizer Management on Soil Aggregates Stability and Fertility in the Loess Plateau, Northern China - Farhat Ullah Khan; Adnan Anwar Khan; Kai Li; Xuexuan Xu; Muhammad Adnan; Shah Fahad; Rafiq Ahmad; Mushtaq Ahmad Khan; Taufiq Nawaz; Faisal Zaman (Journal of Soil Science and Plant Nutrition, 2022)

Plant Growth and Fruit Quality Response of Strawberry is Improved After Exogenous Application of 24-Epibrassinolide - Muhammad Moaaz Ali; Raheel Anwar; Aman Ullah Malik; Ahmad Sattar Khan; Saeed Ahmad; Zahoor Hussain; Mahmood Ul Hasan; Mudassar Nasir; Faxing Chen (Journal of Plant Growth Regulation, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Porostereum spadiceum-AGH786 Regulates the Growth and Metabolites Production in Triticum aestivum L. Under Salt Stress - Syeda Leeda Gul; Yong-Sun Moon; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Muhammad Aaqil Khan; Anwar Hussain; Maryam Shafique; Yoon-Ha Kim; Sajid Ali (Current Microbiology, 2022)

RETRACTED ARTICLE: The nexus between urbanization, renewable energy consumption, financial development, and CO2 emissions: evidence from selected Asian countries - Ahsan Anwar; Avik Sinha; Arshian Sharif; Muhammad Siddique; Shoaib Irshad; Waseem Anwar; Summaira Malik (Environment, Development and Sustainability, 2022)

Evaluating the impact of the environment on depleting groundwater resources: a case study from a semi-arid and arid climatic region - Khalil Ur Rahman; Anwar Hussain; Nuaman Ejaz; Muhammad Shahid; Zheng Duan; Babak Mohammadi; Pham Ngoc Hoai; Quoc Bao Pham; Khaled Mohamed Khedher; Duong Tran Anh (Hydrological Sciences Journal, 2022)

ICP-MS determination of elemental abundance in traditional medicinal plants commonly used in the Kingdom of Saudi Arabia - Rizwan Ahmad; Heba Shaaban; Sahar Y. Issa; Anwar Alsaad; Majd Alghamdi; Njoud Hamid; Rand Osama; Sara Algarni; Ahmed Mostafa; Abdulmalik M. Alqarni; Mohammed Aldholmi; Muhammad Riaz (Food Additives & Contaminants Part B-Surveillance, 2022)

Consumer Perception and Behavior Toward Water Supply, Demand, Water Tariff, Water Quality, and Willingness-To-Pay: A Cross Sectional Study - Toqeer Ahmed; Hassaan Sipra; Muhammad Zahir; Anwar Ahmad; Mumtaz Ahmed (Water Resources Management, 2022)

Heavy metal tolerant endophytic fungi Aspergillus welwitschiae improves growth, ceasing metal uptake and strengthening antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Muhammad Qadir; Amjad Iqbal (Environmental Science and Pollution Research, 2022)

Efficacy of various natural plant extracts and the synthetic insecticide cypermethrin 25EC against Leucinodes orbonalis and their impact on natural enemies in brinjal crop - Mehran Ullah; Farman Ullah; Muhammad Anwar Khan; Shakil Ahmad; Momana Jamil; Sapna Sardar; Kaleem Tariq; Nazeer Ahmed (International Journal of Tropical Insect Science, 2022)

Production of bimodal molecular weight levan by a Lactobacillus reuteri isolate from fish gut - Waqar Ahmad; Anam Nasir; Fazal Sattar; Iram Ashfaq; Ming-Hsu Chen; Azam Hayat; Mujaddad ur Rehman; Sainan Zhao; Shazia Khaliq; Muhammad Afzal Ghauri; Munir Ahmad Anwar (Folia Microbiologica, 2022)

RETRACTED ARTICLE: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2022)

Heterogeneous Pd/C-catalyzed, ligand free Suzuki–Miyaura coupling reaction furnishes new p -terphenyl derivatives - Satya Kumar Avula; Najeeb Ur Rehman; Muhammad U. Anwar; Ghanim Aalthani; Rene Csuk; Ahmed Al-Harrasi (Natural Product Research, 2022)

Ameliorative effect of ethoxylated chalcone-based MAO-B inhibitor on behavioural predictors of haloperidol-induced Parkinsonism in mice: evidence of its antioxidative role against Parkinson’s diseases - Naseer Maliyakkal; Uzma Saleem; Fareeha Anwar; Muhammad Ajmal Shah; Bashir Ahmad; Filzah Umer; Mohammad Ali Abdullah Almoyad; Della Grace Thomas Parambi; Asmy Appadath Beeran; Lekshmi R Nath; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Health concerns among waste collectors during pandemic crisis - Qing Ye; Fahad Asmi; Muhammad Azfar Anwar; Rongting Zhou; Ahmad Nabeel Siddiquei (Environmental Science and Pollution Research, 2022)

Spatio-temporal analysis of climatic variability, trend detection, and drought assessment in Khyber Pakhtunkhwa, Pakistan - Ghani Rahman; Atta-ur Rahman; Muhammad Mushahid Anwar; Muhammad Dawood; Muhammad Miandad (Arabian Journal of Geosciences, 2022)

Reducing cooling load and lifecycle cost for residential buildings: a case of Lahore, Pakistan - Huma Khalid; Muhammad Jamaluddin Thaheem; Muhammad Sohail Anwar Malik; Muhammad Ali Musarat; Wesam Salah Alaloul (The International Journal of Life Cycle Assessment, 2021)

Deep learning-based identification system of weeds and crops in strawberry and pea fields for a precision agriculture sprayer - Shahbaz Khan; Muhammad Tufail; Muhammad Tahir Khan; Zubair Ahmad Khan; Shahzad Anwar (Precision Agriculture, 2021)

Pseudocitrobacter anthropi reduces heavy metal uptake and improves phytohormones and antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Waheed Murad; Muhammad Irshad; Muhammad Qadir; Ho-Youn Kim (World Journal of Microbiology and Biotechnology, 2021)

Environmental quality, forestation, and health expenditure: a cross-country evidence - Muhammad Awais Anwar; Ghulam Rasool Madni; Iftikhar Yasin (Environment, Development and Sustainability, 2021)

Sonolytic-ozonation technology for sanitizing microbial contaminants and pesticide residues from spinach (Spinacia oleracea L.) leaves, at household level - Zarghona Siddique; Aman Ullah Malik; Muhammad Rafique Asi; Raheel Anwar; Muhammad Inam Ur Raheem (Environmental Science and Pollution Research, 2021)

Outer Membrane Protein‐Coated Nanoparticles as Antibacterial Vaccine Candidates - Majid Anwar; Faqir Muhammad; Bushra Akhtar; Muhammad Irfan Anwar; Ahmad Raza; Abdul Aleem (International Journal of Peptide Research and Therapeutics, 2021)

A New Sequential Forward Feature Selection (SFFS) Algorithm for Mining Best Topological and Biological Features to Predict Protein Complexes from Protein–Protein Interaction Networks (PPINs) - Haseeb Younis; Muhammad Waqas Anwar; Muhammad Usman Ghani Khan; Aisha Sikandar; Usama Ijaz Bajwa (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Deciphering the impact of novel coronavirus pandemic on agricultural sustainability, food security, and socio-economic sectors—a review - Mehvish Mumtaz; Nazim Hussain; Zulqarnain Baqar; Saima Anwar; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Production of a broad spectrum streptothricin like antibiotic from halotolerant Streptomyces fimbriatus isolate G1 associated with marine sediments - Neelma Ashraf; Andreas Bechthold; Munir A. Anwar; Muhammad A. Ghauri; Muhammad S. Anjum; Ali N. Khan; Kalsoom Akhtar; Shazia Khaliq (Folia Microbiologica, 2021)

Assessment of groundwater intrinsic vulnerability using GIS-based DRASTIC method in District Haripur, Khyber Pakhtunkhwa, Pakistan - Sohail Ahmed; Anwar Qadir; Mumtaz Ali Khan; Tahseenullah Khan; Muhammad Zafar (Environmental Monitoring and Assessment, 2021)

Coastal Vulnerability of the West Coast of Aceh Besar: A Coastal Morphology Assessment - Muhammad Irham; Ichsan Rusydi; Haekal A. Haridhi; Ichsan Setiawan; Yopi Ilhamsyah; Anwar Deli; Muhammad Rusdi; Annisa Mardiah Siregar (Journal of Marine Science and Engineering, 2021)
The purpose of this study was to determine how vulnerable the west coast of Aceh Besar, Aceh province, Indonesia, is in terms of its coastal morphology. This research was conducted from August to December 2020 and data processing was carried out at the Geographical Information Systems Laboratory, Faculty of Marine Affairs and Fisheries, Syiah Kuala University. The method used was the coastal vulnerability index (CVI) with four geological parameters, namely geomorphological parameters, beach elevation, beach slope and shoreline changes. The results obtained from the CVI method show that 20.60% of the west coast of Aceh Besar, which has a total coastline length of 93.2 km, is in the very high vulnerability category (19.2 km), while 23.18% (21.6 km) is in the high vulnerability category, 8.80% (8.2 km) in the moderate category, 6.44% (6 km) in the low category and 40.99% (38.2 km) in the very low category. Sub-districts classified as having very high vulnerability are Peukanbada (7.94%), Leupung (6.22%), Lhoong (4.94%), and Lhoknga (1.50%). The geomorphology of areas that have very high vulnerability is generally in the form of sandy beaches with a very gentle slope, while, geomorphologically, areas that have very low vulnerability have a high elevation and cliff beaches.

Evaluation of elite bread wheat lines for resistance to blast disease in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Md Babul Anwar; Kishowar-E-Mustarin; Muhammad Rezaul Kabir; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Md Israil Hossain; Xinyao He; Aakash Chawade; Pawan Kumar Singh (Euphytica, 2021)

Genetic architecture of Al3+ toxicity tolerance in rice F2:3 populations determined through QTL mapping - Nusrat Jahan; Muhammad Arshad Javed; Anwar Khan; Fazilah Abd Manan; Bushra Tabassum (Ecotoxicology, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

Neuroprotective potential of Malva neglecta is mediated via down-regulation of cholinesterase and modulation of oxidative stress markers - Uzma Saleem; Rubina Akhtar; Fareeha Anwar; Muhammad Ajmal Shah; Zunera Chaudary; Muhammad Ayaz; Bashir Ahmad (Metabolic Brain Disease, 2021)

Foliar Applied Thiourea Improved Physiological Traits and Yield of Camelina and Canola Under Normal and Heat Stress Conditions - Muhammad Ahmad; Ejaz Ahmad Waraich; Asif Tanveer; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2021)

Effect of co-application of wastewater and freshwater on the physiological properties and trace element content in Raphanus sativus: soil contamination and human health - Natasha; Muhammad Shahid; Aneeza Sardar; Hasnain Anwar; Sana Khalid; Sajid Hussain Shah; Ali Haidar Shah; Muhammad Bilal (Environmental Geochemistry and Health, 2021)

Growth and physio-biochemical responses of maize ( Zea mays L.) to drought and heat stresses - Madiha Ayub; Muhammad Yasin Ashraf; Abida Kausar; Salman Saleem; Sumera Anwar; Volkan Altay; Munir Ozturk (Plant Biosystems, 2021)

RETRACTED ARTICLE: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2021)

Spurring competitiveness, financial and environmental performance of SMEs through government financial and non-financial support - Muhammad Anwar; Shuangjie Li (Environment, Development and Sustainability, 2021)

Intellectual capital, financial resources, and green supply chain management as predictors of financial and environmental performance - Najib Ullah Khan; Muhammad Anwar; Shuangjie Li; Muhammad Sualeh Khattak (Environmental Science and Pollution Research, 2021)

Empirical analysis of CO2 emissions and sustainable use of energy sources in Pakistan - Muhammad Khalid Naeem; Sofia Anwar; Samia Nasreen (Environmental Science and Pollution Research, 2021)

Phytosynthesis of poly (ethylene glycol) methacrylate-hybridized gold nanoparticles from C. tuberculata: their structural characterization and potential for in vitro growth in banana - Natasha Anwar; Jan Wahid; Jalal Uddin; Abbas Khan; Mohib Shah; Syed Adil Shah; Fazle Subhan; Mubarak Ali Khan; Kazim Ali; Mamoona Rauf; Muhammad Arif (In Vitro Cellular & Developmental Biology - Plant, 2021)

Delineating Novel Therapeutic Drug and Vaccine Targets for Staphylococcus cornubiensis NW1T Through Computational Analysis - Mohibullah Shah; Samavia Jaan; Batool Fatima; Muhammad Sameem Javed; Adnan Amjad; Asifullah Khan; Sahib Gul Afridi; Umar Nishan; Anwar Iqbal; Haq Nawaz (International Journal of Peptide Research and Therapeutics, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Chemiluminescent-microparticle-immunoassay-based detection and prevalence of human immunodeficiency virus infection in Islamabad, Pakistan - Misbahud Din; Faheem Anwar; Muhammad Ali; Muhammad Yousaf; Bilal Ahmad; Abdullah (Archives of Virology, 2021)

Influence of tourism, governance, and foreign direct investment on energy consumption and CO2 emissions: a panel analysis of Muslim countries - Faqeer Muhammad; Anwar Khan; Naveed Razzaq; Rehmat Karim (Environmental Science and Pollution Research, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Combined application of Bacillus sp. MN-54 and phosphorus improved growth and reduced lead uptake by maize in the lead-contaminated soil - Muhammad Junaid Afzal; Muhammad Imran Khan; Sardar Alam Cheema; Saddam Hussain; Muhammad Anwar-ul-Haq; Muhammad Hayder Ali; Muhammad Naveed (Environmental Science and Pollution Research, 2020)

The role of sense of place, risk perception, and level of disaster preparedness in disaster vulnerable mountainous areas of Gilgit-Baltistan, Pakistan - Garee Khan; Javed Akhter Qureshi; Anwar Khan; Attaullah Shah; Sajid Ali; Iram Bano; Muhammad Alam (Environmental Science and Pollution Research, 2020)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Risk assessment of heavy metal(loid)s via Spinacia oleracea ingestion after sewage water irrigation practices in Vehari District - Aneeza Sardar; Muhammad Shahid; Natasha; Sana Khalid; Hasnain Anwar; Muhammad Tahir; Ghulam Mustafa Shah; Muhammad Mubeen (Environmental Science and Pollution Research, 2020)

Environmental concerns and switching toward electric vehicles: geographic and institutional perspectives - Aqsa Sajjad; Fahad Asmi; Jianxun Chu; Muhammad Azfar Anwar (Environmental Science and Pollution Research, 2020)

QTL mapping for field resistance to wheat blast in the Caninde#1/Alondra population - Xinyao He; Muhammad Rezaul Kabir; Krishna K. Roy; Md. Babul Anwar; Kaijie Xu; Felix Marza; Firuz Odilbekov; Aakash Chawade; Etienne Duveiller; Eric Huttner; Pawan K. Singh (Theoretical and Applied Genetics, 2020)
Key message Wheat blast resistance in Caninde#1 is controlled by a major QTL on 2NS/2AS translocation and multiple minor QTL in an additive mode. Abstract Wheat blast (WB) is a devastating disease in South America, and it recently also emerged in Bangladesh. Host resistance to WB has relied heavily on the 2NS/2AS translocation, but the responsible QTL has not been mapped and its phenotypic effects in different environments have not been reported. In the current study, a recombinant inbred line population with 298 progenies was generated, with the female and male parents being Caninde#1 (with 2NS) and Alondra (without 2NS), respectively. Phenotyping was carried out in two locations in Bolivia, namely Quirusillas and Okinawa, and one location in Bangladesh, Jashore, with two sowing dates in each of the two cropping seasons in each location, during the years 2017–2019. Genotyping was performed with the DArTseq® technology along with five previously reported STS markers in the 2NS region. QTL mapping identified a major and consistent QTL on 2NS/2AS region, explaining between 22.4 and 50.1% of the phenotypic variation in different environments. Additional QTL were detected on chromosomes 1AS, 2BL, 3AL, 4BS, 4DL and 7BS, all additive to the 2NS QTL and showing phenotypic effects less than 10%. Two codominant STS markers, WGGB156 and WGGB159 , were linked proximally to the 2NS/2AS QTL with a genetic distance of 0.9 cM, being potentially useful in marker-assisted selection.

Iron Nutrition Improves Productivity, Profitability, and Biofortification of Bread Wheat under Conventional and Conservation Tillage Systems - Usman Zulfiqar; Muhammad Maqsood; Saddam Hussain; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Human Biomonitoring of Trace Elements in Scalp Hair from Healthy Population of Pakistan - Fouzia Noreen; Ashif Sajjad; Khalid Mahmood; Muhammad Anwar; Manzar Zahra; Amir Waseem (Biological Trace Element Research, 2020)

Occurrence of heavy metals and pesticide residues in tomato crop: a threat to public health - Muhammad Ishaq; Nighat Sultana; Muhammad Ikram; Amjad Iqbal; Farooq Shah; Muhammad Hamayun; Anwar Hussain (Arabian Journal of Geosciences, 2020)

Yucasin and cinnamic acid inhibit IAA and flavonoids biosynthesis minimizing interaction between maize and endophyte Aspergillus nomius - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Abdul Tawab; Naeem Khan (Symbiosis, 2020)

Nephroprotective effects of curcumin loaded chitosan nanoparticles in cypermethrin induced renal toxicity in rabbits - Maira Anwar; Faqir Muhammad; Bushra Akhtar; Sajjad ur Rehman; Muhammad Kashif Saleemi (Environmental Science and Pollution Research, 2020)

Shigella flexneri: an emerging pathogen - Iqbal Nisa; Muhammad Qasim; Nusrat Yasin; Rafi Ullah; Anwar Ali (Folia Microbiologica, 2020)

Short stay, long impact: ecological footprints of sojourners - Qing Ye; Muhammad Azfar Anwar; Rongting Zhou; Fahad Asmi; Intikhab Ahmad (Environmental Science and Pollution Research, 2020)

Organochlorine pesticides in the surrounding soils of POPs destruction facility: source fingerprinting, human health, and ecological risks assessment - Syeda Nazish Ali; Mujtaba Baqar; Mehvish Mumtaz; Uzma Ashraf; Muhammad Naveed Anwar; Abdul Qadir; Sajid Rashid Ahmad; Abdul-Sattar Nizami; Huang Jun (Environmental Science and Pollution Research, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

Influence of biochar amendment and foliar application of iron oxide nanoparticles on growth, photosynthesis, and cadmium accumulation in rice biomass - Muhammad Rizwan; Shamaila Noureen; Shafaqat Ali; Sarwat Anwar; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Azhar Hussain (Journal of Soils and Sediments, 2019)

Climate change communication as political agenda and voters’ behavior - Muhammad Azfar Anwar; Rongting Zhou; Aqsa Sajjad; Fahad Asmi (Environmental Science and Pollution Research, 2019)

Effect of expression of additional catalytic domain on characteristics of Xylanase Z of Clostridium thermocellum - Muhammad Imran Mahmood Khan; Muddassar Zafar; Zahid Anwar; Muhammad Imran (Biologia, 2019)

Long-term changes of a waterbird community over 26 years at a Pakistani Ramsar Site - Imran Khaliq; Muhammad Irshad Arshad; Anwar Hussain Gill; Abdul Aleem Chaudhry; Muhammad Anwer Maan; Muhammad Anwar Iqbal; Muhamad Akbar; Diana E. Bowler (Wetlands Ecology and Management, 2019)

Growth-promoting bioactivities of Bipolaris sp. CSL-1 isolated from Cannabis sativa suggest a distinctive role in modifying host plant phenotypic plasticity and functions - Lubna; Sajjad Asaf; Abdul Latif Khan; Muhammad Waqas; Sang-Mo Kang; Muhammad Hamayun; In-Jung Lee; Anwar Hussain (Acta Physiologiae Plantarum, 2019)

Combined use of biochar and zinc oxide nanoparticle foliar spray improved the plant growth and decreased the cadmium accumulation in rice (Oryza sativa L.) plant - Shafaqat Ali; Muhammad Rizwan; Shamaila Noureen; Sarwat Anwar; Basharat Ali; Muhammad Naveed; Elsayed Fathi Abd_Allah; Abdulaziz A. Alqarawi; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Synthesis of 4-formyl pyridinium propylthioacetate stabilized silver nanoparticles and their application in chemosensing of 6-aminopenicillanic acid (APA) - A. Anwar; M. R. Shah; S. P. Muhammad; K. Ali; N. A. Khan (International Journal of Environmental Science and Technology, 2019)

Characterization of Hydrocarbon-Degrading Bacteria in Constructed Wetland Microcosms Used to Treat Crude Oil Polluted Water - Amer Jamal Hashmat; Muhammad Afzal; Kaneez Fatima; Muhammad Anwar-ul-Haq; Qaiser Mahmood Khan; Carlos A. Arias; Hans Brix (Bulletin of Environmental Contamination and Toxicology, 2019)

In vitro production of IAA by endophytic fungus Aspergillus awamori and its growth promoting activities in Zea mays - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Naeem Khan (Symbiosis, 2019)

Seismic vulnerability of non-ductile RC buildings in Pakistan through stochastic analysis of design/construction deficiencies - Muhammad Usman Ali; Shaukat Ali Khan; Muhammad Yousaf Anwar; Uzair Maqbool (Bulletin of Earthquake Engineering, 2019)

Identification of Genes Involved in Flavonoid Biosynthesis of Chinese Narcissus (Narcissus tazetta L. var. chinensis) - Guiqing Wang; Biyun Yang; Jiacheng Wu; Peng Luo; Muhammad Anwar; Andrew C. Allan; Kui Lin-Wang; Richard V. Espley; Lihui Zeng (Plant Molecular Biology Reporter, 2018)

Effect of distillery spentwash fertigation on crop growth, yield, and accumulation of potentially toxic elements in rice - Sadiq Naveed; Abdur Rehim; Muhammad Imran; Muhammad Faraz Anwar; Saddam Hussain (Environmental Science and Pollution Research, 2018)

A natural flavonoid lawsonaringenin induces cell cycle arrest and apoptosis in HT-29 colorectal cancer cells by targeting multiple signalling pathways - Areeba Anwar; Nizam Uddin; Bina Shaheen Siddiqui; Rafat Ali Siddiqui; Sabira Begum; Muhammad Iqbal Choudhary (Molecular Biology Reports, 2018)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Evidence of genetically diverse virulent mating types of Phytophthora capsici from Capsicum annum L. - Kiran Nawaz; Ahmad Ali Shahid; Louis Bengyella; Muhammad Nasir Subhani; Muhammad Ali; Waheed Anwar; Sehrish Iftikhar; Shinawar Waseem Ali (World Journal of Microbiology and Biotechnology, 2018)

Voltage dependence of the Ca2+ transient in endocardial and epicardial myocytes from the left ventricle of Goto–Kakizaki type 2 diabetic rats - Lina Al Kury; Vadym Sydorenko; Manal M. A. Smail; Muhammad Anwar Qureshi; Anatoliy Shmygol; Murat Oz; Jaipaul Singh; Frank Christopher Howarth (Molecular and Cellular Biochemistry, 2018)

Development of streamflow prediction models for a weir using ANN and step-wise regression - Muhammad Hassan; Haseeb Zaffar; Imran Mehmood; Anwar Khitab (Modeling Earth Systems and Environment, 2018)

The genus Luteovirus from infection to disease - Muhammad Ali; Sidra Anwar; Malik Nawaz Shuja; Rajiv Kumar Tripathi; Jaswinder Singh (European Journal of Plant Pathology, 2018)

Effects of increasing dietary protein supplies on milk yield, milk composition, and nitrogen use efficiency in lactating buffalo - Muhammad Naveed-ul-Haque; Muhammad Uzair Akhtar; Rizwan Munnawar; Saba Anwar; Anjum Khalique; Murtaza Ali Tipu; Fayyaz Ahmad; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2018)

First report of leaf spot caused by Phytophthora capsici on chili pepper (Capsicum frutescens L.) in Pakistan - Kiran Nawaz; Ahmad Ali Shahid; Muhammad Nasir Subhani; Sehrish Iftikhar; Waheed Anwar (Journal of Plant Pathology, 2018)

Identification of a new begomovirus infecting Duranta repens in Pakistan - Sidra Anwar; Muhammad Tahir (Archives of Virology, 2018)

Evaluation of immunostimulatory and immunotherapeutic effects of tropical mushroom (Lentinus edodes) against eimeriasis in chicken - Muhammad Irfan Ullah; Masood Akhtar; Mian Muhammad Awais; Muhammad Irfan Anwar; Kashfa Khaliq (Tropical Animal Health and Production, 2018)

Evaluating groundwater quality for irrigated agriculture: spatio-temporal investigations using GIS and geostatistics in Punjab, Pakistan - Muhammad Awais; Muhammad Arshad; Syed Hamid Hussain Shah; Muhammad Anwar-ul-Haq (Arabian Journal of Geosciences, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Felsic dykes in the Neoproterozoic Nagar Parkar Igneous Complex, SE Sindh, Pakistan: geochemistry and tectonic settings - Tahseenullah Khan; Mamoru Murata; M. Qasim Jan; Hafiz Ur Rehman; Muhammad Zafar; Hiroaki Ozawa; Anwar Qadir; Saqib Mehmood (Arabian Journal of Geosciences, 2017)

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

Expression studies of chitinase gene in transgenic potato against Alternaria solani - Anwar Khan; Idrees Ahmad Nasir; Bushra Tabassum; Khadija Aaliya; Muhammad Tariq; Abdul Qayyum Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Comparative Study of Physical Factors and Microbial Diversity of Four Man-Made Extreme Ecosystems - Imran Ali; Ali Akbar; Muhammad Aslam; Sami Ullah; Muhammad Anwar; Hunsa Punnapayak; Pongtharin Lotrakul; Sehanat Prasongsuk; Benjawan Yanwisetpakdee; Ponlada Permpornsakul; Sudip K. Rakshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The potential of precision surface irrigation in the Indus Basin Irrigation System - Arif A. Anwar; Waqas Ahmad; Muhammad Tousif Bhatti; Zia Ul Haq (Irrigation Science, 2016)

Uptake and distribution of minerals and heavy metals in commonly grown leafy vegetable species irrigated with sewage water - Sumera Anwar; Muhammad Farrakh Nawaz; Sadaf Gul; Muhammad Rizwan; Shafaqat Ali; Arshaad Kareem (Environmental Monitoring and Assessment, 2016)

Phytoremediation: recent advances in plant-endophytic synergistic interactions - Amna Ijaz; Asma Imran; Muhammad Anwar ul Haq; Qaiser M. Khan; Muhammad Afzal (Plant and Soil, 2016)

Phenolic, flavonoid contents, anticholinesterase and antioxidant evaluation of Iris germanica var ; florentina - Farhat Ullah; Muhammad Ayaz; Abdul Sadiq; Abid Hussain; Sajjad Ahmad; Muhammad Imran; Anwar Zeb (Natural Product Research, 2016)

Therapeutic Efficacy of Neurostimulation for Depression: Techniques, Current Modalities, and Future Challenges - Hafsah Akhtar; Faiza Bukhari; Misbah Nazir; Muhammad Nabeel Anwar; Adeeb Shahzad (Neuroscience Bulletin, 2016)

Escherichia coli expression of NDV fusion protein gene and determination of its antigenic epitopes - Naila Shahid; Sana Tahir; Abdul Q. Rao; Sameera Hassan; Anwar Khan; Ayesha Latif; Muhammad Au Khan; Bushra Tabassum; Ahmed A. Shahid; Ahmed U. Zafar; Tayyab Husnain (Biologia, 2015)

Development of sediment load estimation models by using artificial neural networking techniques - Muhammad Hassan; M. Ali Shamim; Ali Sikandar; Imran Mehmood; Imtiaz Ahmed; Syed Zishan Ashiq; Anwar Khitab (Environmental Monitoring and Assessment, 2015)

Solvent Effect on the Photolysis of Riboflavin - Iqbal Ahmad; Zubair Anwar; Sofia Ahmed; Muhammad Ali Sheraz; Raheela Bano; Ambreen Hafeez (AAPS PharmSciTech, 2015)

Cancer initiating properties of erythrosine supplemented with sub necrotic dose of diethyl nitrosamine: potential effects on biochemical parameters of liver, Vitamin C and E - Firoz Anwar; Rajbala Singh; Gohar Mushtaq; Abdul Rehman Al-Maliki; Abdullah Sabih; F. A. Al-Abbasi; Aftab Ahmad; Muhammad Afzal; Imran Kazmi; Ruqaiyah Khan (Molecular & Cellular Toxicology, 2015)

The effect of gestational diabetes on proliferation capacity and viability of human umbilical cord-derived stromal cells - Nadia Wajid; Rashida Naseem; Sanam Saiqa Anwar; Sana Javaid Awan; Muhammad Ali; Sara Javed; Fatima Ali (Cell and Tissue Banking, 2015)

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.) - Shafaqat Ali; Aaifa Chaudhary; Muhammad Rizwan; Hafiza Tania Anwar; Muhammad Adrees; Mujahid Farid; Muhammad Kashif Irshad; Tahir Hayat; Shakeel Ahmad Anjum (Environmental Science and Pollution Research, 2015)

Environmental quality indicators and financial development in Malaysia: unity in diversity - Arif Alam; Muhammad Azam; Alias Bin Abdullah; Ihtisham Abdul Malik; Anwar Khan; Tengku Adeline Adura Tengku Hamzah; Faridullah; Muhammad Mushtaq Khan; Hina Zahoor; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Phylogenetic characterization and novelty of organic sulphur metabolizing genes of Rhodococcus spp. (Eu-32) - Nasrin Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Shaun Heaphy (Biotechnology Letters, 2015)

Seleniferous soils as a source for production of selenium-enriched foods and potential of bacteria to enhance plant selenium uptake - Muhammad Yasin; Ali F. El Mehdawi; Courtney E. Jahn; Aneela Anwar; Marie F. S. Turner; Muhammad Faisal; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2015)

Characterization of Reactive Red-120 Decolorizing Bacterial Strain Acinetobacter junii FA10 Capable of Simultaneous Removal of Azo Dyes and Hexavalent Chromium - Faiza Anwar; Sabir Hussain; Shahla Ramzan; Farhan Hafeez; Muhammad Arshad; Muhammad Imran; Zahid Maqbool; Naila Abbas (Water, Air, & Soil Pollution, 2014)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

Monitoring impacts of air pollution: PIXE analysis and histopathological modalities in evaluating relative risks of elemental contamination - Sohail Ejaz; Gerry Amor Camer; Khaleeq Anwar; Muhammad Ashraf (Ecotoxicology, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

MRI and neuropathological validations of the involvement of air pollutants in cortical selective neuronal loss - Sohail Ejaz; Khaleeq Anwar; Muhammad Ashraf (Environmental Science and Pollution Research, 2014)

Therapeutic exploration of betulinic acid in chemically induced hypothyroidism - Muhammad Afzal; Imran Kazmi; Susmita Semwal; Fahad A. Al-Abbasi; Firoz Anwar (Molecular and Cellular Biochemistry, 2014)

Combination of sulfamethoxazole and selenium in anticancer therapy: a novel approach - Ritu Gupta; Imran Kazmi; Muhammad Afzal; Ruqaiyah Khan; Mohit Chauhan; Fahad A. Al-Abbasi; Aftab Ahmad; Firoz Anwar (Molecular and Cellular Biochemistry, 2013)

Anticancer effect of ursolic acid stearoyl glucoside in chemically induced hepatocellular carcinoma - Imran Kazmi; Anil Raj Narooka; Muhammad Afzal; Rajbala Singh; Fahad A. Al-Abbasi; Aftab Ahmad; Firoz Anwar (Journal of Physiology and Biochemistry, 2013)

Root Colonization and Phytostimulation by Phytohormones Producing Entophytic Nostoc sp. AH-12 - Anwar Hussain; Muhammad Hamayun; Syed Tariq Shah (Current Microbiology, 2013)

Polypharmacy (herbal and synthetic drug combination): a novel approach in the treatment of type-2 diabetes and its complications in rats - Rupinder Kaur; Muhammad Afzal; Imran Kazmi; Iqbal Ahamd; Zubair Ahmed; Babar Ali; Sayeed Ahmad; Firoz Anwar (Journal of Natural Medicines, 2013)

Cytotoxic, phytotoxic, and mutagenic appraisal to ascertain toxicological potential of particulate matter emitted from automobiles - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Imran Altaf; Aftab Ahmad Anjum (Environmental Science and Pollution Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Hepatoprotective potential of new steroid against carbon tetrachloride-induced hepatic injury - Muhammad Afzal; Ruqaiyah Khan; Imran Kazmi; Firoz Anwar (Molecular and Cellular Biochemistry, 2013)

Population structure and linkage disequilibrium in Lupinus albus L. germplasm and its implication for association mapping - Muhammad Javed Iqbal; Sujan Mamidi; Rubina Ahsan; Shahryar F. Kianian; Clarice J. Coyne; Anwar A. Hamama; Satya S. Narina; Harbans L. Bhardwaj (Theoretical and Applied Genetics, 2012)

Seasonal prevalence of coccidiosis in industrial broiler chickens in Faisalabad, Punjab, Pakistan - Mian Muhammad Awais; Masood Akhtar; Zafar Iqbal; Faqir Muhammad; Muhammad Irfan Anwar (Tropical Animal Health and Production, 2012)

Antihaemorrhagic potentials of Fagonia cretica against Naja naja karachiensis (black Pakistan cobra) venom - Muhammad Tahir Razi; Muhammad Hassham Hassan Bin Asad; Taous Khan; Muhammad Zabta Chaudhary; Muhammad Tayyab Ansari; Muhammad Anwar Arshad; Qazi Najam-us Saqib (Natural Product Research, 2011)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

The chronic effects of neonatal alloxan-induced diabetes mellitus on ventricular myocyte shortening and cytosolic Ca2+ - Frank Christopher Howarth; Zahra Hassan; Muhammad Anwar Qureshi (Molecular and Cellular Biochemistry, 2011)

Growth promotion of cucumber by pure cultures of gibberellin-producing Phoma sp. GAH7 - Muhammad Hamayun; Sumera Afzal Khan; Abdul Latif Khan; Dong-Sheng Tang; Javid Hussain; Bashir Ahmad; Yasir Anwar; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2010)

Detection of Mycobacterium avium subsp. paratuberculosis in tissue samples of cattle and buffaloes - Farhan Anwar Khan; Zafar Iqbal Chaudhry; Muhammad Ijaz Ali; Shahid Khan; Naima Mumtaz; Ijaz Ahmad (Tropical Animal Health and Production, 2010)

Effect of induced pyrexia on the disposition kinetics of ciprofloxacin in dogs - Faqir Muhammad; Masood Akhtar; M. Irfan Anwar; M. Javed Arshed (Veterinary Research Communications, 2009)

Gene structure and mutant alleles of PCDH15: nonsyndromic deafness DFNB23 and type 1 Usher syndrome - Zubair M. Ahmed; Saima Riazuddin; Sandar Aye; Rana A. Ali; Hanka Venselaar; Saima Anwar; Polina P. Belyantseva; Muhammad Qasim; Sheikh Riazuddin; Thomas B. Friedman (Human Genetics, 2008)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Relationship among acidophilic bacteria from diverse environments as determined by randomly amplified polymorphic DNA analysis (RAPD) - Tanveer Akbar; Kalsoom Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Moazur Rehman; Mehboobur Rehman; Yusuf Zafar; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2005)

Urban and peri-urban aquaculture as an immediate source of food fish: Perspectives of Dhaka City, Bangladesh - MD. Shahidul Islam; Muhammad Tanvir Hossain Chowdhury; MD. Mokhlesur Rahman; MD. Anwar Hossain (Urban Ecosystems, 2004)

Technical communication: Determination of cuprous ions in bacterial leachates and for environmental monitoring - Munir A. Anwar; Mazhar Iqbal; Muhammad A. Qamar; Moazur Rehman; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2000)